Biaxially oriented polyester film and method for producing the same
By using a polyester resin composition of a specific crystallization temperature and carrying out a specific tensile treatment, the shortcomings of the existing biaxially oriented polyester films in terms of impact strength and heat resistance are solved, and efficient impact strength and heat resistance are achieved.
Patent Information
- Application Number
- CN202080083384.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-20
- Filing Date
- 2020-12-16
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2040-12-16
AI Technical Summary
The existing biaxially oriented polyester films have shortcomings in impact strength and heat resistance, and cannot meet the requirements for impact strength at high temperatures.
By using a polyester resin composition containing a specific crystallization temperature, the stretching treatment is performed using a specific temperature range and a stretching ratio to form a biaxially oriented polyester film with excellent moldability.
It achieves excellent impact strength and heat resistance of biaxially oriented polyester films, and is suitable for packaging, optical and high-temperature treatment and other purposes.
Smart Images

Figure GDA0004005951420000491 
Figure GDA0004005951420000511 
Figure GDA0004005951420000521
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a biaxially oriented polyester film, and more particularly to a method for producing a biaxially oriented polyester film having excellent flexibility, moldability, and heat resistance. Background Art
[0002] Films made of polyesters having excellent crystallinity, such as polyethylene terephthalate resin, are excellent in mechanical properties, heat resistance, etc., and are being used in a variety of applications.
[0003] For example, it is used in a wide range of applications such as packaging, electrical insulation, optics, magnetic recording, and release substrates.
[0004] However, biaxially oriented films made of polyesters having excellent crystallinity, such as polyethylene terephthalate resin, are excellent in heat resistance, but cannot satisfy impact strength.
[0005] In this regard, a biaxially oriented polyester film mainly composed of a polyester resin having low crystallinity, such as a polyethylene terephthalate resin copolymerized with isophthalic acid or an aliphatic polyester, has excellent impact strength but is inferior in heat resistance.
[0006] As a method for reducing the heat shrinkage rate of a biaxially stretched film formed of a polyethylene terephthalate resin at a high temperature, there is shown a method of making the temperature during stretching in the width direction sufficiently higher than the crystallization temperature and then setting it to a temperature extremely close to the heat setting temperature (for example, refer to Patent Document 1), but the impact strength is insufficient.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2017-74750 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] An object of the present invention is to solve the above-mentioned problems and provide a biaxially oriented polyester film having excellent impact strength and heat resistance and a method for producing the same.
[0012] More specifically, the present invention aims to provide a biaxially stretched polyester film which is less likely to have pinholes or breakage in the film when bent or impacted, and has little dimensional change in the film heating process such as printing processing, and a method for stably producing the same at low cost.
[0013] Solutions for solving problems
[0014] The present inventors have conducted intensive studies to achieve the above-mentioned purpose, and as a result, have found that when manufacturing a biaxially oriented polyester film containing a layer formed by a composition including a polyester resin having a specific crystallization temperature, an unstretched sheet formed by the aforementioned polyester resin composition is stretched in a specific temperature range and at a specific stretch ratio in the length direction and the width direction, thereby obtaining a biaxially oriented film excellent in impact strength and heat resistance.
[0015] It should be noted that by using a composition containing a polyester resin having a specific crystallization temperature, a soft biaxially oriented polyester film with excellent formability can also be formed. This film is suitable for use in applications such as secondary battery exterior materials and labels in addition to general packaging.
[0016] The present invention is as described below. [1]
[0018] A method for producing a biaxially stretched polyester film comprises the following steps A to D.
[0019] Tc represents the crystallization temperature (°C), Tg represents the glass transition temperature (°C), and Tm represents the melting point (°C).
[0020] (Step A): A step of melt-extruding a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C to 35°C to obtain an unstretched polyester resin composition sheet.
[0021] (Step B): The unstretched polyester resin composition sheet obtained in step A is heated in the range of Tg+5(°C) or higher and Tg+40(°C) or lower of the polyester resin, and stretched in the longitudinal direction in the range of a stretching ratio of 2 times or higher and 6 times or lower, to obtain a uniaxially oriented polyester resin composition film.
[0022] (Step C): The uniaxially oriented polyester resin composition film obtained in step B is heated in the range of Tc-46 (°C) or higher and Tc+25 (°C) or lower of the polyester resin, and stretched in the width direction in the range of a stretching ratio of 4 times or higher and 8 times or lower, to obtain a biaxially oriented polyester resin composition film.
[0023] (Step D): A step of relaxing the biaxially oriented polyester resin composition film obtained in step C within a range of 3% to 20% in the width direction of the film while heating the film within a range of Tm-40 (°C) or higher and Tm-5 (°C) or lower. [2]
[0025] A method for producing a biaxially stretched polyester film comprises the following steps A to D.
[0026] Tc represents the crystallization temperature (°C), Tg represents the glass transition temperature (°C), and Tm represents the melting point (°C).
[0027] (Step A): A step of melt-coextruding a layer composed of a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C to 35°C and a layer composed of a polyester resin composition to obtain an unstretched polyester resin composition sheet.
[0028] (Step B): The unstretched polyester resin composition sheet obtained in step A is heated in the range of Tg+5(°C) or higher and Tg+40(°C) or lower of the polyester resin, and stretched in the longitudinal direction in the range of a stretching ratio of 2 times or higher and 6 times or lower, to obtain a uniaxially oriented polyester resin composition film.
[0029] (Step C): The uniaxially oriented polyester resin composition film obtained in step B is heated in the range of Tc-46 (°C) or higher and Tc+25 (°C) or lower of the polyester resin, and stretched in the width direction in the range of a stretching ratio of 4 times or higher and 8 times or lower, to obtain a biaxially oriented polyester resin composition film.
[0030] (Step D): A step of relaxing the biaxially oriented polyester resin composition film obtained in step C within a range of 3% to 20% in the width direction of the film while heating the film within a range of Tm-40 (°C) or higher and Tm-5 (°C) or lower. [3]
[0032] A biaxially oriented polyester film is formed from a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C to 35°C, and satisfies the following (1) to (3).
[0033] Tc represents the crystallization temperature (°C), Tg represents the glass transition temperature (°C), and Tm represents the melting point (°C).
[0034] (1) The maximum value of the heat shrinkage stress in the longitudinal direction above Tg (° C.) of the polyester resin is 0.1 MPa to 4.0 MPa.
[0035] (2) The heat shrinkage in the longitudinal direction when treated at 150° C. for 30 minutes is 0.1% or more and 3.0% or less.
[0036] (3) Impact strength is 0.5 J / 12 μm or more and 1.0 J / 12 μm or less. [4]
[0038] A biaxially oriented polyester film comprising: a layer formed from a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C to 35°C; and a layer formed from a polyester resin composition, and satisfying the following (1) to (3).
[0039] Tc represents the crystallization temperature (°C), Tg represents the glass transition temperature (°C), and Tm represents the melting point (°C).
[0040] (1) The maximum value of the heat shrinkage stress in the longitudinal direction above Tg (° C.) of the polyester resin is 0.1 MPa to 4.0 MPa.
[0041] (2) The heat shrinkage in the longitudinal direction when treated at 150° C. for 30 minutes is 0.1% or more and 3.0% or less.
[0042] (3) Impact strength is 0.5 J / 12 μm or more and 1.0 J / 12 μm or less. [5]
[0044] A method for producing a biaxially oriented polyester film satisfying the following (1) to (3), comprising the following steps A to D.
[0045] Tc represents the crystallization temperature (°C), Tg represents the glass transition temperature (°C), and Tm represents the melting point (°C).
[0046] (1) The maximum value of the heat shrinkage stress in the longitudinal direction above Tg (° C.) of the polyester resin is 0.1 MPa to 4.0 MPa.
[0047] (2) The heat shrinkage in the longitudinal direction when treated at 150° C. for 30 minutes is 0.1% or more and 3.0% or less.
[0048] (3) Impact strength is 0.5 J / 12 μm or more and 1.0 J / 12 μm or less.
[0049] (Step A): A step of melt-extruding a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C or higher and 30°C or lower to obtain an unstretched polyester resin composition sheet.
[0050] (Step B): The unstretched polyester resin composition sheet obtained in step A is heated in the range of Tg+5(°C) or higher and Tg+40(°C) or lower of the polyester resin, and stretched in the longitudinal direction in the range of a stretching ratio of 2 times or higher and 6 times or lower, to obtain a uniaxially oriented polyester resin composition film.
[0051] (Step C): The uniaxially oriented polyester resin composition film obtained in step B is heated in the range of Tc-46 (°C) or higher and Tc+25 (°C) or lower of the polyester resin, and stretched in the width direction in the range of a stretching ratio of 4 times or higher and 8 times or lower, to obtain a biaxially oriented polyester resin composition film.
[0052] (Step D): A step of relaxing the biaxially oriented polyester resin composition film obtained in step C within a range of 3% to 20% in the width direction of the film while heating the film within a range of Tm-40 (°C) to Tm (°C) of the polyester resin. [6]
[0054] A method for producing a biaxially oriented polyester film satisfying the following (1) to (3), comprising the following steps A to D.
[0055] Tc represents the crystallization temperature (°C), Tg represents the glass transition temperature (°C), and Tm represents the melting point (°C).
[0056] (1) The maximum value of the heat shrinkage stress in the longitudinal direction above Tg (° C.) of the polyester resin is 0.1 MPa to 4.0 MPa.
[0057] (2) The heat shrinkage in the longitudinal direction when treated at 150° C. for 30 minutes is 0.1% or more and 3.0% or less.
[0058] (3) Impact strength is 0.5 J / 12 μm or more and 1.0 J / 12 μm or less,
[0059] (Step A): a step of melt-coextruding a layer formed of a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C to 35°C and a layer formed of a polyester resin composition to obtain an unstretched polyester resin composition sheet,
[0060] (Step B): a step of heating the unstretched polyester resin composition sheet obtained in step A within a range of Tg+5(°C) or higher and Tg+40(°C) or lower of the polyester resin, and stretching the unstretched polyester resin composition sheet in a longitudinal direction within a range of a stretching ratio of 2 to 6 to obtain a uniaxially oriented polyester resin composition film.
[0061] (Step C): a step of heating the uniaxially oriented polyester resin composition film obtained in step B within a range of Tc-46 (°C) of the polyester resin and below Tc+25 (°C) of the polyester resin, and stretching the film in the width direction within a range of a stretching ratio of 4 to 8 times to obtain a biaxially oriented polyester resin composition film,
[0062] (Step D): A step of relaxing the biaxially oriented polyester resin composition film obtained in step C within a range of 3% to 20% in the width direction of the film while heating the film within a range of Tm-40 (°C) to Tm (°C) of the polyester resin.
[0063] Effects of the Invention
[0064] The biaxially stretched polyester film of the present invention has excellent impact strength and heat resistance. Therefore, it can be used for packaging and optical purposes by exerting its mechanical strength, and can be particularly suitable for post-processing at high temperatures and for purposes requiring stable thermal dimensional stability at high temperatures. DETAILED DESCRIPTION
[0065] In the present invention, it is preferred to use a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C to 35°C. This can improve the impact strength. From the viewpoint of impact strength, Tc-(Tg+Tm) / 2 is more preferably -10°C to 30°C, further preferably 0°C to 30°C, and particularly preferably 5°C to 25°C.
[0066] A polyester resin having a Tc-(Tg+Tm) / 2 of not less than -25°C and not more than 35°C has the property of slow crystallization rate and excellent impact resistance derived from the soft amorphous component. A method for controlling Tc-(Tg+Tm) / 2 of a polyester resin to fall within the range of not less than -25°C and not more than 30°C is effective in having monomers such as a polyester resin having no rigid structure, for example, an aromatic dicarboxylic acid having a bent structure, a soft aliphatic dicarboxylic acid, a sterically large diol, and a soft aliphatic monocarboxylic acid monool.
[0067] One specific example of the polyester resin used in the present invention is a polyester resin obtained by copolymerizing ethylene glycol and terephthalic acid as main components, and at least one monomer selected from the group consisting of isophthalic acid, p-β-oxyethoxybenzoic acid, 2,6-naphthalene dicarboxylic acid, 4,4'-dicarboxybenzophenone, bis-(4-carboxyphenylethane), adipic acid, sebacic acid, glutaric acid, succinic acid, 2,5-furan dicarboxylic acid, sodium 5-sulfoisophthalic acid, and cyclohexane-1,4-dicarboxylic acid as a dicarboxylic acid component other than terephthalic acid. The content of these monomers is preferably 3 mol% to 30 mol%, more preferably 5 mol% to 15 mol%, and the monomers are more preferably isophthalic acid, adipic acid, sebacic acid, glutaric acid, and 2,5-furan dicarboxylic acid.
[0068] Alternatively, it is a polyester resin obtained by copolymerizing at least one monomer selected from the group consisting of propylene glycol, butanediol, neopentyl glycol, diethylene glycol, cyclohexanedimethanol, ethylene oxide adducts such as bisphenol A, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol as a diol component other than ethylene glycol. The content of these monomers is preferably 3 mol% to 30 mol%, more preferably 5 mol% to 15 mol%, and the monomers are more preferably neopentyl glycol and diethylene glycol.
[0069] The polyester resin used in the present invention may contain a diol component other than ethylene glycol and a dicarboxylic acid component other than terephthalic acid in combination.
[0070] Another specific example of the polyester resin used in the present invention may be a single crystalline polyester formed of a bent dicarboxylic acid and ethylene glycol.
[0071] In addition, the raw materials used are preferably those derived from plants, those obtained by chemical recovery, etc., in addition to those derived from fossil resources. Examples of the raw materials derived from plants include bio-ethylene glycol, bio-propylene glycol, bio-butylene glycol, bio-adipic acid, bio-sebacic acid, bio-glutaric acid, bio-terephthalic acid, and bio-furan dicarboxylic acid. Examples of the raw materials obtained by chemical recovery include recovered terephthalic acid, recovered isophthalic acid, recovered naphthalene dicarboxylic acid, and recovered furan dicarboxylic acid.
[0072] There is no particular limitation on the method for producing these polyester resins. That is, those produced by any method of transesterification or direct polymerization can be used. In addition, in order to increase the molecular weight and reduce the amount of oligomers, those produced by solid phase polymerization can also be used.
[0073] The intrinsic viscosity of these polyester resins is preferably in the range of 0.57 dl / g to 1.0 dl / g, and more preferably in the range of 0.60 dl / g to 0.90 dl / g.
[0074] If the intrinsic viscosity of the polyester resin is lower than 0.57 dl / g, the film becomes easily broken. In addition, when the intrinsic viscosity of the polyester resin is reduced, the crystallization temperature of the polyester resin is increased, and the heat resistance of the obtained biaxially oriented polyester film is improved. If the intrinsic viscosity of the polyester resin is higher than 1.0 dl / g, the resin pressure in the extrusion process increases, and extrusion becomes difficult. In addition, when the intrinsic viscosity of the polyester resin is increased, the crystallization temperature of the polyester resin is reduced, and the impact strength of the obtained biaxially oriented polyester film is improved.
[0075] As another specific example of the polyester resin used in the present invention, a crystalline polylactic acid resin as an aliphatic polyester can also be cited. The crystalline polylactic acid resin is obtained by ring-opening polymerization of lactide using a compound having a hydroxyl group as an initiator in the presence of a known catalyst, and the optical purity of the lactide used is preferably high, that is, the ratio of L-lactic acid (hereinafter L-isomer) / D-lactic acid (hereinafter D-isomer) is 100 / 0 to 85 / 15 (weight %) or 15 / 85 to 0 / 100 (weight %). When the L-isomer ratio is 85 weight % or more or 15 weight % or less, the crystallinity is sufficient, the melting point is increased, and heat resistance is obtained, so it is preferred.
[0076] The glass transition point of the crystalline polylactic acid resin is preferably 30° C. or higher and 70° C. or lower, more preferably 35° C. or higher and 70° C. or lower, and further preferably 35° C. or higher and 65° C. or lower.
[0077] When the glass transition temperature is 35°C or higher, the optical purity is high and the crystallinity is easily improved. In addition, the melting point is preferably 120 to 175°C. When the melting point is 120°C or higher, the optical purity is high and the crystallinity is easily improved. The glass transition point and melting point can be obtained by a scanning calorimeter (DSC).
[0078] Furthermore, the crystalline polylactic acid resin is preferably capable of oriented crystallization. The melt flow rate (210°C / 2.16kg condition) as an indicator of the fluidity of the crystalline polylactic acid resin is preferably 3 g / min or more and 100 g / min or less, more preferably 3 g / min or more and 50 g / min or less, further preferably 4 g / min or more and 30 g / min or less, and further preferably 5 g / min or more and 25 g / min or less. If the melt flow rate is 3 g / min or more, the viscosity during melt molding will not be excessively increased, and it is not easy to observe a decrease in productivity. If the melt flow rate is 100 g / min or less, it is not easy to become brittle, and it is not easy to observe a decrease in strength.
[0079] The molecular weight of the crystalline polylactic acid resin used in the present invention is preferably in the range of 50,000 to 300,000, more preferably 70,000 to 250,000, and further preferably 80,000 to 200,000. When the molecular weight is 100,000 or more, the resin is not easily brittle. When the molecular weight is 300,000 or less, the melt viscosity is not easily increased, and the processability such as melt moldability is not easily reduced.
[0080] The crystalline polylactic acid resin can be easily obtained by a melt ring-opening polymerization method from lactide as a raw material.
[0081] Examples of commercially available polylactic acid resins include Ingeo, an L-type polymer manufactured by Nature Works, REVODA manufactured by Zhejiang Hisun Biomaterials, and Luminy, a polylactic acid resin manufactured by Corbion.
[0082] The polyester resin composition in the present application may contain various additives such as lubricants, antistatic agents, hiding agents, colorants, defoaming agents, antistatic agents, ultraviolet absorbers, melt viscosity increasing agents, adhesion agents, barrier agents, antioxidants, thermal stability agents, plasticizers, crystal nucleating agents, etc.
[0083] Specific examples of additives include inorganic lubricants such as titanium dioxide, fine silica, kaolin, zirconium oxide, magnesium oxide, and calcium carbonate, organic lubricants such as crosslinked polymers formed by acrylic monomers such as acrylic acid, methacrylic acid, acrylates, and methacrylates, alkyl sulfonates, polyfunctional isocyanates, polyfunctional carbodiimide compounds, polyfunctional epoxy compounds, aliphatic and aromatic polyester resins, polyurethane resins, polycarbonate resins, acrylic resins, vinyl resins, low molecular weight barrier agents, polyglycolic acids, antioxidants such as Irganox 1010 (manufactured by Ciba Japan), polyglycerols, polymerization catalyst deactivators such as phosphorus compounds, etc. Two or more additives may be used in combination.
[0084] The melting point of additives other than the inorganic compound is preferably 200° C. or lower. When the melting point is 200° C. or lower, these resins are easily melted in the molten polyester resin and are unlikely to cause poor appearance.
[0085] The amount of these additives added is appropriately adjusted to achieve the desired properties, and is preferably in the range of 0 to 10% by weight. When it is 10% by weight or less, the various properties are less likely to be degraded.
[0086] The method for producing the biaxially stretched polyester film of the present invention is described below. The method for producing the biaxially stretched polyester film of the present invention preferably includes the following steps A to D in order. Tc represents the crystallization temperature (°C), Tg represents the glass transition temperature (°C), and Tm represents the melting point (°C).
[0087] (Step A): A step of melt-extruding a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C to 35°C to obtain an unstretched polyester resin composition sheet.
[0088] (Step B): The unstretched polyester resin composition sheet obtained in step A is heated in the range of Tg+5(°C) or higher and Tg+40(°C) or lower of the polyester resin, and stretched in the longitudinal direction in the range of a stretching ratio of 2 times or higher and 6 times or lower, to obtain a uniaxially oriented polyester resin composition film.
[0089] (Step C): The uniaxially oriented polyester resin composition film obtained in step B is heated in the range of Tc-46 (°C) or higher and Tc+25 (°C) or lower of the polyester resin, and stretched in the width direction in the range of a stretching ratio of 4 times or higher and 8 times or lower, to obtain a biaxially oriented polyester resin composition film.
[0090] (Step D): A step of relaxing the biaxially oriented polyester resin composition film obtained in step C within a range of 3% to 20% in the width direction of the film while heating the film within a range of Tm-40 (°C) or higher and Tm-5 (°C) or lower.
[0091] Each process is explained in detail.
[0092] (Process A)
[0093] First, pellets of a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C or higher and 35°C or lower are dried so that the moisture content becomes lower than 100 ppm.
[0094] Next, the pellets are supplied to an extruder, heated to a temperature above the melting point of the polyester resin, for example, 280° C., and melted, and melt-extruded from a T-die into a sheet. Furthermore, the molten sheet is brought into close contact with a rotating metal roll set at 23° C. by an electrostatic application method, and cooled and solidified to obtain an unstretched sheet. The extrusion temperature in the extruder is a temperature above the melting point, and is appropriately adjusted according to the resin used.
[0095] When laminating with a thermoplastic resin of another composition, in addition to the general co-extrusion method, it is also preferable to use a film forming process and a coating method after film forming.
[0096] For example, pellets of a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C to 35°C are dried to a moisture content of less than 100 ppm, and a polyester resin composition having a different composition is prepared.
[0097] Next, the layers are heated to a temperature above the melting point and melted by two or more extruders, respectively, and fed out from different flow paths, and laminated into multiple layers by a multilayer feed head, a static mixer, a multilayer multi-manifold die, etc. Alternatively, only one extruder may be used, and the multilayering device may be introduced into the melting line from the extruder to the T-die.
[0098] Next, the multilayered molten resin composition was melt-extruded from a T-die into a sheet. The molten sheet was then brought into close contact with a rotating metal roll set at 23° C. by electrostatic application and cooled to solidify, thereby obtaining an unstretched sheet.
[0099] (Process B)
[0100] Next, the obtained unstretched sheet is stretched in the longitudinal direction. The stretching in the longitudinal direction is preferably performed as follows: the unstretched polyester resin composition sheet obtained in step A is heated in the range of Tg+5 (°C) or more of the polyester resin and Tg+40 (°C) or less of the polyester resin, and stretched in the longitudinal direction at a stretching ratio of 2 times or more and 6 times or less to obtain a uniaxially oriented polyester resin composition film.
[0101] By stretching in the longitudinal direction within this range, the birefringence {Nx-(Ny+Nz)} / 2 of the obtained uniaxially oriented film can easily be 0.03 or more and 0.10 or less.
[0102] The longitudinal direction stretching temperature is more preferably Tg+10(°C) or higher, and further preferably Tg+15°C or higher. It is more preferably Tg+35(°C) or lower, and further preferably Tg+28°C or lower.
[0103] Even if the polyester resin is not easily crystallized, by setting the birefringence {Nx-(Ny+Nz)} / 2 of the obtained uniaxially oriented film to 0.03 or more and 0.10 or less, the orientation and crystallinity of the film can be increased in the subsequent step C.
[0104] It should be noted that Nx, Ny, and Nz refer to the refractive index in the length direction, width direction, and thickness direction of the film, respectively.
[0105] The birefringence of the polyester resin film stretched in the longitudinal direction may be measured by any method such as sampling the film stretched in the longitudinal direction, measuring with an Abbe refractometer, or using an online birefringence meter. Any measuring method may be used.
[0106] (Process C)
[0107] Next, the uniaxially oriented polyester resin composition film obtained in step B is heated in the range of Tc-46 (°C) or higher and Tc+25 (°C) or lower of the polyester resin, and stretched in the width direction in the range of a stretching ratio of 4 times or higher and 8 times or lower to obtain a biaxially oriented polyester resin composition film.
[0108] It is believed that when a polyester resin contains Tc-(Tg+Tm) / 2 of above -25°C and below 35°C, if the stretching temperature in the width direction is above Tc-46(°C), the thermal mobility of the polyester molecules will not easily decrease, and the recrystallization caused by orientation will be easily promoted.
[0109] It is also considered that if it is Tc+25(°C) or lower, crystallites serving as crystallization nuclei are easily generated, or the stress applied to the film during stretching in the width direction is less likely to decrease, and the polyester molecular chains are more easily oriented, so that crystallization is more likely to proceed.
[0110] The stretching temperature in the width direction is more preferably Tc-30 (°C) or higher, and further preferably Tc-15 (°C) or higher. It is more preferably Tc+18 (°C) or lower.
[0111] It is believed that if the stretch ratio is 4 times or more, the orientation of the polyester molecular chain is also easy, so crystallization is easy to advance. If the stretch ratio is 8 times or less, it is not easy to break. The stretch ratio is more preferably 5 times or more, and further preferably 5.5 times or more.
[0112] (Process D)
[0113] The biaxially oriented polyester resin composition film obtained in step C is heated in the range of Tm-40 (°C) or higher and Tm-5 (°C) or lower of the polyester resin, and is relaxed in the range of 3% or higher and 20% or lower in the width direction of the film. In the above temperature range, the amorphous part can be sufficiently relaxed without reducing the crystallinity, and the shrinkage stress and heat shrinkage rate of the finally obtained biaxially oriented polyester can be reduced.
[0114] If the value obtained by subtracting the plane orientation coefficient of the film after step D without performing step C from the plane orientation coefficient of the film after step D is 0 or more and 0.04 or less, it means that the increase in crystallinity of the film before and after step D is small or the same.
[0115] In addition, by setting the value obtained by subtracting the density of the film after step D without performing step C from the density of the film after step D to 0.001 or more and 0.012 or less, the heat shrinkage rate can be further reduced, and the strength of the film, specifically, the impact strength can be further improved.
[0116] The polyester resin is preferably heated within a range of Tm-30°C to Tm-5°C, preferably within a range of Tm-20°C to Tm-7°C, and more preferably relaxed within a range of 3% to 20%.
[0117] (Stretchability)
[0118] In steps A to C, and particularly in steps B to D, breakage may occur, but it is preferred that thin film collection can be performed, and it is more preferred that no breakage of the thin film occurs.
[0119] (Thin film characteristics)
[0120] The biaxially oriented polyester film of the present invention preferably satisfies the following (1) to (3).
[0121] Here, the "longitudinal direction" in the biaxially oriented polyester film of the present invention refers to a direction corresponding to a flow direction in the film production process, and the "width direction" refers to a direction perpendicular to the flow direction in the film production process.
[0122] (1) The maximum value of the heat shrinkage stress in the longitudinal direction above Tg (° C.) of the polyester resin is 0.1 MPa to 4.0 MPa.
[0123] (2) The heat shrinkage in the longitudinal direction when treated at 150° C. for 30 minutes is 0.1% or more and 3.0% or less.
[0124] (3) Impact strength is 0.5 J / 12 μm or more and 1.0 J / 12 μm or less.
[0125] When the biaxially oriented polyester film is a laminated film, the polyester resin used in (1) has a Tg (°C) of Tc-(Tg+Tm) / 2 of -25°C to 35°C.
[0126] Each characteristic is described.
[0127] (1) Thermal shrinkage stress in the longitudinal direction The biaxially oriented polyester film of the present invention preferably has a maximum value of thermal shrinkage stress above the glass transition temperature of 0.1 MPa to 4.0 MPa. If the maximum value of thermal shrinkage stress above the glass transition temperature of the film is 4.0 MPa or less, the tension does not become excessively large in the steps of heating and conveying the film, such as printing, protective coating, and drying, and thus the processed appearance is excellent. If the maximum value of thermal shrinkage stress above the glass transition temperature of the film is 0.1 MPa or more, tension is appropriately generated in the steps of heating the film, such as printing, protective coating, and drying, and thus printing is easy.
[0128] The maximum value of the heat shrinkage stress above the glass transition temperature is more preferably 0.5 MPa to 3.6 MPa, further preferably 1.0 MPa to 3.3 MPa, particularly preferably 1.5 MPa to 3.0 MPa.
[0129] (2) Thermal shrinkage in the longitudinal direction
[0130] The biaxially oriented polyester film of the present invention preferably has a heat shrinkage in the longitudinal direction of 0.1% or more and 3.0% or less when treated at 150°C for 30 minutes. Even if the maximum value of the heat shrinkage stress above the glass transition temperature in the longitudinal direction of the film is 0.1 MPa or more and 4.0 MPa or less, if the heat shrinkage in the longitudinal direction of the film when treated at 150°C for 30 minutes exceeds 3.0%, the dimensional change is likely to become large in the process of heat sealing at high temperature such as bag making, and therefore, the bag shape appearance and durability are insufficient.
[0131] The heat shrinkage rate in the longitudinal direction of the film when treated at 150° C. for 30 minutes is more preferably 0.3% to 2.7%, further preferably 0.3% to 2.4%, and further preferably 0.5% to 2.3%.
[0132] (3) Impact strength
[0133] The impact strength of the biaxially oriented polyester film of the present invention is 0.5 J / 12 μm or more and 1.0 J / 12 μm or less. If the impact strength is 0.5 J / 12 μm, pinholes and breakage are not easily generated in the film when it is bent or impacted, and the durability is excellent. The impact strength is preferably 0.55 J / 12 μm or more, and more preferably 0.6 J / 12 μm or more. As long as the impact strength is about 1.0 J / 12 μm, the durability is sufficient.
[0134] (Suitability for printing processing)
[0135] The appearance of the film obtained by gravure printing the gravure ink on the biaxially oriented polyester film of the present invention and drying to form a printed ink layer may be good in appearance. Even if wrinkles or sags are slightly visible, the flatness may be good, and no wrinkles are more preferred.
[0136] (Processing suitability)
[0137] After coating the biaxially oriented polyester film of the present invention with a polyester adhesive, dry lamination or extrusion lamination with a polyethylene film or polypropylene film having a thickness of 20 to 60 μm is performed, a sandwich body is formed with aluminum foil, etc., and the film is aged at 30 to 50°C to obtain a laminate that can be used for packaging bags.
[0138] A packaging bag can be produced by stacking two such laminates with the olefin film side facing inward and heat-sealing them at a temperature not higher than the melting point of the olefin film.
[0139] (Bag breaking characteristics)
[0140] The packaging bag prepared above is filled with water and other contents, and the operation of dropping from a certain height, for example, 1m, is repeated. The bag breaking property can be evaluated according to the number of times until the bag breaks or leaks. Preferably, it is 2 times or more, more preferably 5 times or more. When it is less than 1 time, it will cause practical obstacles to the transportation of the packaged goods. Most preferably, there is no bag breaking or leaking even after 5 times. If a film with high film impact strength is used, the bag breaking property is excellent.
[0141] (Container cover material)
[0142] The film of the present invention can also be used as a cover material for sealing the opening of a container.
[0143] As a method for sealing the lid film to the container, various methods such as ultrasonic sealing and impulse sealing can be used in addition to general heat sealing. Particularly preferred are sealing using a general heat sealing bar and sealing by ultrasonic sealing.
[0144] When sealing is performed by ultrasonic sealing, it is preferred to provide a resin composition layer having a sealing layer. However, based on the principle of this method, bonding can sometimes be performed even without a resin composition layer having a sealing layer. In such a case, it is not necessary to provide a resin composition layer having a sealing layer.
[0145] In the case where the resin composition layer having a sealing layer is not provided on the film side, a method of providing a resin composition layer having a heat-sealable layer on the surface around the opening of the container may be adopted.
[0146] As a preferred method for sealing the opening of a container, the following methods can be cited: a method in which a resin composition layer having sealing properties is provided on one side of the biaxially oriented polyester film of the present invention; and a method in which the resin composition layer side of the biaxially oriented polyester film of the present invention having a layer having sealing properties on the surface side is bonded to the peripheral surface of the opening of the container.
[0147] The resin composition having sealing properties preferably contains a polyester resin as a main component. In addition, the resin composition having sealing properties preferably has easy peelability such that the sealing strength after sealing the non-container is weakened so that the lid material can be easily opened from the container.
[0148] For the polyester resin used as the base polymer of the resin composition having sealing properties, various polyester resins having a lower melting point and crystallinity than the polyester resin on the substrate side can be used. For example, as a polycarboxylic acid, it is desirable that terephthalic acid is 40 mol% or more, and as a diol component, it is desirable that butanediol is 80 mol% or more. If terephthalic acid is less than 40 mol% and butanediol is less than 80 mol%, the melting point decreases, and it becomes difficult to perform retort sterilization at high temperatures. In addition, the crystallization rate decreases, and blocking occurs when the film is rolled up during film making.
[0149] As polyester resin, if it is within the above range, other components can also be copolymerized. As the polycarboxylic acid component at this time, known substances such as isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, furandicarboxylic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, capric acid, dimer acid, cyclohexane dicarboxylic acid, and trimellitic acid can be used. In addition, as the diol component, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,4-butanediol, pentanediol, 3-methylpentanediol, hexanediol, nonanediol, cyclohexanedimethanol, and trimethylolpropane can be used.
[0150] In order to properly adjust the sealing strength to make the peelability good, in addition to the main component polyester resin, a polyolefin resin can also be contained. In the case of blending polyolefin resins, the blending amount is preferably 3 to 20% by weight, more preferably 8 to 20% by weight. By containing an appropriate amount of polyolefin resin, peelability with appropriate peel strength (for example, a peel strength of 1 to 2 kgf / 15mm) can be achieved. In fact, when peeling by hand, in order to obtain particularly excellent peelability, that is, a good peeling feel, it is preferred to blend more than 3% by weight of polyolefin resin. However, when the blending amount is too much, there is a tendency for the sealing strength to weaken, and there is a further tendency for the fragrance to decrease, therefore, problems such as resin smell and adsorption of the contents of the container are generated. As the added polyolefin resin, polyethylene, polypropylene, polybutene, ionomers, ethylene propylene copolymers, ethylene butene copolymers, propylene butene copolymers, etc. can be used.
[0151] The glass transition temperature of the polyester resin used as the base polymer of the resin composition having sealing properties is preferably 0° C. or lower, more preferably -5° C. or lower. If the glass transition temperature is too high, the volume shrinkage of the crystalline polyester during crystallization tends to increase, and the adhesiveness to crystalline polyethylene terephthalate tends to decrease significantly.
[0152] The melting point of the polyester resin used as the base polymer of the resin composition having sealing properties is preferably 120 to 200°C, more preferably 120 to 180°C. If the melting point is too low, the adhesive layer will whiten and deform during cooking, the appearance may deteriorate, and the sealing strength is likely to be significantly reduced. If the melting point is too high, the sealing temperature must be increased. If the sealing temperature is too high, the C-PET is likely to soften and deform, resulting in poor appearance. In terms of film formability, the intrinsic viscosity of the crystalline polyester is generally preferably about 0.5 to 2.0.
[0153] When 5 to 60% by weight of polyether diol is copolymerized in a polyester resin used as a base polymer of a resin composition having sealing properties, good peelability can be obtained. If there is too little polyether diol, the adhesive force is too strong and it tends to be difficult to peel off. In addition, in the case of too much (for example, more than 60% by weight), the adhesiveness tends to decrease, and the amount of decomposed polyether diol increases, generating odor. As a result, the fragrance is poor. And the polyether diol at this time is preferably polytetramethylene glycol. By using it, the molecular weight can be increased to a suitable molecular weight for use as an easy-to-peel sealant, and good peelability can be obtained.
[0154] The melting point of the polyester resin used as the base polymer of the resin composition having sealing properties must be lower than the melting point of the substrate side. The difference between the melting point of the substrate side and the melting point of the sealing layer side is 1 to 50°C, preferably 5 to 50°C, and more preferably 10 to 50°C. The sealing temperature is set between the melting points of the two. When it is high, it is also advantageous from the perspective of sealing strength. However, if it is less than 1°C, the substrate side will also melt during sealing, and confidentiality cannot be maintained due to pinholes and damage, so it is not preferred. When it is above 50°C, the effect in terms of sealing properties reaches saturation.
[0155] As the sealing layer composition, if it is considered that the cover material and the container are recovered at the same time after use, it is preferred that the composition is close to that of the base material / container side. For example, a small amount of other resin components can be added to the composition of the base material / container side, and a small amount of other raw materials can be copolymerized. In order to maximize the reduction of the melting point, copolymerization is preferably used. In this case, the copolymerization amount is not limited by the type of component, and it must be a similar resin when it is in the range of 5 to 60%, preferably 8 to 60%, and more preferably 10 to 60% by weight ratio in addition / copolymerization.
[0156] The melting point of the polyester resin used as the base polymer of the sealing resin composition is preferably lower than the melting point of the polyester resin of the biaxially oriented polyester film as the substrate, or lower than the melting point of the polyester resin constituting a layer other than the sealing resin composition layer of the laminated biaxially oriented polyester film.
[0157] The difference between the melting point of the polyester resin of the substrate and the melting point of the polyester resin used as the base polymer of the resin composition layer having sealing properties is 1 to 50°C, preferably 5 to 50°C, and more preferably 10 to 50°C.
[0158] The sealing temperature is set between the melting points of the two. When it is high, it is also advantageous from the perspective of sealing strength. However, if it is less than 1°C, the polyester resin of the base material will also melt during sealing, and confidentiality cannot be maintained due to pinholes and damage, so it is not preferred. When it is above 50°C, the effect on sealing reaches saturation.
[0159] For resin compositions with sealing properties, when considering using a cover material and a container for simultaneous recovery, those with similar compositions are preferred. For example, a small amount of other resin components can be added to the composition on the substrate / container side, or a small amount of other raw materials can be copolymerized. In order to maximize the reduction in melting point, copolymerization is preferably used.
[0160] For the polyester resin used in the present invention, in order to cope with the current environmental problems, it is preferable to use recycled resin, plant-derived resin, etc. In the case of recycled resin, resin obtained by recycling / reusing PET (polyethylene terephthalate) resin bottles is suitable. For plant-derived resin, it is preferable to use a resin obtained by using a method of analysis based on ISO. 14 The resin having a biomass content of 1 to 100%, more preferably 3 to 100%. When the biomass content is 1% or less, the CO generated by the plant-derived raw material is used. 2 The effect of reducing emissions is small.
[0161] Furthermore, various additives may be added to the sealing resin composition as required. For example, as a lubricant, the aforementioned inorganic lubricant or organic lubricant may be used, and as an antistatic agent, stearic acid monoglyceride or sorbitan polyoxyethylene may be used. In addition, a small amount of polyolefin resin, polyamide, polycarbonate, etc. may be contained as required within the range that does not significantly change its characteristics.
[0162] The thickness of the resin composition layer having sealing properties is preferably in the range of 0.15 to 20 μm, more preferably 0.2 to 10 μm, further preferably 0.3 to 8 μm, further preferably 0.5 to 8 μm, and particularly preferably 1.0 to 8 μm. If the thickness of the sealing layer is 0.1 μm or more, the sealing strength is easily reflected, and the thickness is sufficient as long as it is about 20 μm. From the viewpoint of recyclability, the thickness of the sealing layer is preferably 12 μm or less. More preferably, it is 10 μm or less, more preferably 8 μm or less, and further preferably 4 μm or less.
[0163] The thickness of the film for lid material having sealing properties can be arbitrarily determined according to its application, but is generally about 20 to 150 μm. Other suitable known adhesives may be used to laminate on the resin composition layer having sealing properties.
[0164] (container)
[0165] After the container is filled with food, it can be sealed using the biaxially oriented polyester film of the present invention as a cover material and then used as a packaging material such as various packaging containers. The container can also be used as a container with excellent heat resistance that can withstand retort treatment, etc. by crystallizing. For example, it can be sterilized by retort sterilization, or can be heated in a microwave oven or an electric oven, and can also be used as a container for retort food, microwave oven, or electric oven heating food.
[0166] The container based on the combination of the polyester resin used in the cover film formed by the film of the present invention and the container formed by the polyester resin with a similar composition to the polyester resin used in the cover film has excellent original characteristics such as excellent flavor retention, heat resistance and moldability, and is also excellent in recyclability after use. In addition, no harmful substances are generated when incinerated for disposal, and the waste disposal suitability and environmental suitability are extremely excellent. Therefore, it is one of the preferred embodiments.
[0167] In this case, if the container is made of a material with high barrier properties, it becomes a barrier container made of a single raw material, which is one of the more preferred methods of use. The barrier properties of the material used are 2000 ml / m 2 / d / MPa or less, preferably 500ml / m 2 / d / MPa, most preferably 200ml / m 2 / d / MPa.
[0168] (Polyester resin composition for container)
[0169] In the present invention, the biaxially oriented polyester film or the container using the laminated biaxially oriented polyester film as a lid material is preferably formed from a polyester resin composition.
[0170] (Polyester resin)
[0171] As one specific example of the polyester resin used in the polyester resin composition constituting the container, there can be mentioned a polyester resin containing ethylene glycol and terephthalic acid as constituent components.
[0172] Another specific example of the polyester resin used in the polyester resin composition constituting the container is a polyester resin obtained by copolymerizing ethylene glycol and terephthalic acid as main components, and at least one monomer selected from the group consisting of isophthalic acid, p-β-oxyethoxybenzoic acid, 2,6-naphthalene dicarboxylic acid, 4,4'-dicarboxybenzophenone, bis-(4-carboxyphenylethane), adipic acid, sebacic acid, glutaric acid, succinic acid, 2,5-furan dicarboxylic acid, sodium 5-sulfoisophthalic acid, and cyclohexane-1,4-dicarboxylic acid as a dicarboxylic acid component other than terephthalic acid. The content of these monomers is preferably 3 mol% or more and 30 mol% or less, more preferably 5 mol% or more and 15 mol% or less, and the monomer is more preferably isophthalic acid, adipic acid, sebacic acid, glutaric acid, and 2,5-furan dicarboxylic acid.
[0173] Alternatively, it is a polyester resin obtained by copolymerizing at least one monomer selected from the group consisting of propylene glycol, butanediol, neopentyl glycol, diethylene glycol, cyclohexanedimethanol, ethylene oxide adducts of bisphenol A, etc., polyethylene glycol, polypropylene glycol, and polytetramethylene glycol as a diol component other than ethylene glycol. The content of these monomers is preferably 3 mol% to 30 mol%, more preferably 5 mol% to 15 mol%, and the monomers are more preferably neopentyl glycol and diethylene glycol.
[0174] The polyester resin used in the present invention may contain a diol component other than ethylene glycol and a dicarboxylic acid component other than terephthalic acid in combination.
[0175] Another specific example of the polyester resin used in the polyester resin composition constituting the container may be a single crystalline polyester formed of a bent dicarboxylic acid and ethylene glycol.
[0176] In addition to the raw materials derived from fossil resources, it is also preferred to use raw materials derived from plants or obtained through chemical recycling. Examples of raw materials derived from plants include bio-ethylene glycol, bio-propylene glycol, bio-butylene glycol, bio-adipic acid, bio-sebacic acid, bio-glutaric acid, bio-terephthalic acid, and bio-furan dicarboxylic acid. Examples of raw materials obtained through chemical recycling include recycled terephthalic acid, recycled isophthalic acid, recycled naphthalene dicarboxylic acid, and recycled furan dicarboxylic acid.
[0177] There is no particular limitation on the method for producing these polyester resins. That is, those produced by any method of transesterification or direct polymerization can be used. In addition, in order to increase the molecular weight and reduce the amount of oligomers, those produced by solid phase polymerization can also be used.
[0178] The intrinsic viscosity of these polyester resins is preferably in the range of 0.57 dl / g to 1.2 dl / g, and more preferably in the range of 0.60 dl / g to 1.00 dl / g.
[0179] When the intrinsic viscosity of the polyester resin is 0.57 dl / g or more, the impact resistance can be easily improved. When the intrinsic viscosity of the polyester resin is 1.2 dl / g or less, the resin pressure in the molding process increases, making it difficult to mold the container.
[0180] As another specific example of the polyester resin used in the polyester resin composition constituting the container, a crystalline polylactic acid resin as an aliphatic polyester can also be cited. The crystalline polylactic acid resin can be obtained by ring-opening polymerization of lactide using a compound having a hydroxyl group as an initiator in the presence of a known catalyst. The lactide used is preferably one with high optical purity, that is, the ratio of L-lactic acid (hereinafter L-isomer) / D-lactic acid (hereinafter D-isomer) is 100 / 0 to 85 / 15 (weight %) or 15 / 85 to 0 / 100 (weight %). When the L-isomer ratio is 85 weight % or more or 15 weight % or less, the crystallinity is sufficient, and the melting point is increased, and heat resistance is obtained, so it is preferred.
[0181] The glass transition point of the crystalline polylactic acid resin is preferably 30° C. or higher and 70° C. or lower, more preferably 35° C. or higher and 70° C. or lower, and further preferably 35° C. or higher and 65° C. or lower.
[0182] When the glass transition temperature is 35° C. or higher, the optical purity is high and the crystallinity is easily improved.
[0183] The melting point is preferably 120 to 175° C. When the melting point is 120° C. or higher, the optical purity is high and the crystallinity is easily improved. The glass transition point and melting point can be obtained by a scanning calorimeter (DSC).
[0184] Furthermore, the crystalline polylactic acid resin is preferably capable of oriented crystallization. The melt flow rate (210°C / 2.16kg condition) as an indicator of the fluidity of the crystalline polylactic acid resin is preferably 3 g / min or more and 100 g / min or less, more preferably 3 g / min or more and 50 g / min or less, further preferably 4 g / min or more and 30 g / min or less, and further preferably 5 g / min or more and 25 g / min or less. If the melt flow rate is 3 g / min or more, the viscosity during melt molding will not be excessively increased, and it is not easy to observe a decrease in productivity. If the melt flow rate is 100 g / min or less, it is not easy to become brittle, and it is not easy to observe a decrease in strength.
[0185] The molecular weight of the crystalline polylactic acid resin is preferably in the range of 100,000 to 300,000, more preferably 100,000 to 250,000, and further preferably 100,000 to 200,000. When the molecular weight is 100,000 or more, the resin is not easily brittle. When the molecular weight is 300,000 or less, the melt viscosity is not easily increased, and the processability such as melt moldability is not easily reduced.
[0186] The crystalline polylactic acid resin can be easily obtained by a melt ring-opening polymerization method from lactide as a raw material.
[0187] Examples of commercially available polylactic acid resins include Ingeo, an L-type polymer manufactured by Nature Works, REVODA manufactured by Zhejiang Hisun Biomaterials, and Luminy, a polylactic acid resin manufactured by Corbion.
[0188] (catalyst)
[0189] When producing the polyester resin used in the polyester resin composition constituting the container, various polymerization catalysts can be used. Antimony-based, germanium-based, titanium-based catalysts can be used, but aluminum-based catalysts can also be preferably used from the perspective of recyclability.
[0190] In addition, Al compounds used in the production of polyester resins include carboxylates such as aluminum formate, aluminum acetate, aluminum propionate, and aluminum oxalate, oxides, inorganic acid salts such as aluminum hydroxide, aluminum chloride, aluminum hydroxide chlorohydrate, and aluminum carbonate, aluminum alkoxides such as aluminum methoxide and aluminum ethoxide, aluminum chelate compounds such as aluminum acetylacetonate and aluminum acetylacetate, organic aluminum compounds such as trimethylaluminum and triethylaluminum, and partial hydrolyzates thereof. Among them, aluminum acetate, aluminum chloride, aluminum hydroxide, aluminum hydroxide chlorohydrate, aluminum lactate, and aluminum acetylacetonate are particularly preferred. The Al compound is preferably added in a range of 5 to 200 ppm based on the Al residual amount in the resulting polymer.
[0191] In addition, in the case of Al compounds, alkali metal compounds or alkaline earth metal compounds may also be used in combination. Examples of alkali metal compounds or alkaline earth metal compounds include carboxylates such as acetates of these elements, alkoxides, etc., which are added to the reaction system as powders, aqueous solutions, ethylene glycol solutions, etc. The alkali metal compounds or alkaline earth metal compounds are preferably added in a range of 1 to 50 ppm based on the residual amount of these elements in the generated polymer. The aforementioned catalyst compound may be added at any stage of the aforementioned polyester formation reaction step.
[0192] In addition, various phosphorus compounds can be used as stabilizers. As the phosphorus compounds used, phosphoric acid, phosphorous acid, phosphonic acid and their derivatives can be cited. As specific examples, phosphoric acid, trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, monomethyl phosphate, dimethyl phosphate, monobutyl phosphate, dibutyl phosphate, phosphorous acid, trimethyl phosphite, triethyl phosphite, tributyl phosphite, methylphosphonic acid, dimethyl methylphosphonate, dimethyl ethylphosphonate, dimethyl phenylphosphonate, diethyl phenylphosphonate, diphenyl phenylphosphonate, etc., which can be used alone or in combination of two or more. The phosphorus compound is preferably added at any stage of the polyester formation reaction step in such a manner that the phosphorus residual amount in the generated polymer is in the range of 5 to 100 ppm.
[0193] (Thin pieces)
[0194] In the process of flake-forming the melt-polycondensed polymer, solid-phase polymerization, conveying the melt-polycondensed polymer flakes, and solid-phase polymerization of the polymer flakes, etc., which constitute the manufacturing process of the polyester resin, granules, powders, etc., which are much smaller than the size originally set during granulation, are produced. Here, such fine granules, powders, etc. are called fine flakes. Such fine flakes are highly crystallized due to the shear force and impact force they are subjected to, and have the property of promoting the crystallization of the polyester resin. By controlling their content, the crystallization characteristics of the flakes can be controlled.
[0195] Here, the fine pieces refer to powders or fragments that pass through a sieve equipped with a metal mesh having an aperture of 1.7 mm in accordance with JIS-Z8801, and are measured according to the method described in Examples.
[0196] As a method for adjusting the content of fine flakes in the polyester resin to the aforementioned range, for example, in addition to a method based on mixing small pieces of polyester with a high content of fine flakes that have not passed the screening process with small pieces of polyester with a very small content of fine flakes that have passed the screening process and the air flow-based fine flake removal process in an appropriate proportion, it is also possible to use: adjusting by changing the aperture of the sieve in the fine flake removal process, and any method based on changing the screening speed, etc.
[0197] In addition, flaky PET obtained by purifying and recovering a container formed of used polyester resin by various recovery methods such as mechanical recovery and chemical recovery, and small flake polyester resin obtained by melt-extruding the flaky PET may be mixed and used.
[0198] (Lubricant)
[0199] The polyester resin composition may contain the aforementioned lubricant such as inorganic fine particles and an organic lubricant.
[0200] Examples of inorganic fine particles include talc, mica, calcium carbonate, magnesium carbonate, titanium oxide, aluminum oxide, silicon dioxide, silicate, barium sulfate, wollastonite, kaolin, carbon black, and zinc oxide.
[0201] The shape of the inorganic fine particles formed of such an inorganic substance may be any particle shape such as spherical, needle-like, plate-like, scale-like, or crushed, and is not particularly limited.
[0202] The average particle size of the inorganic fine particles used is preferably The lower limit of the average particle size is preferably When the particle size is small, that is, less than 0.1 μm, especially less than 0.01 μm, it is easy to cause secondary aggregation when mixed with the polyester as a matrix, which not only destroys the effect of the nucleating agent, but also has the disadvantage of reducing the appearance and quality of the molded product due to the aggregation.
[0203] The polyester resin composition may contain wax. By containing wax, the roughness of the surface of the polyester sheet for containers is eliminated, or the inorganic particles that function as a crystal nucleating agent are easily dispersed more finely in the polyester resin composition, and the effects are easily enhanced compared to the case where the inorganic particles are added alone.
[0204] Furthermore, environmental hormones and the like are currently receiving attention, and waxes with low risk, harmfulness and environmental impact to the human body are desired.
[0205] In this regard, biodegradable wax is useful. Specific examples of biodegradable wax include: lignite wax, carnauba wax, castor wax, candelilla wax, rice bran wax and other plant waxes, beeswax and other animal waxes, natural paraffin and other hydrocarbon waxes, stearic acid and other fatty acid waxes, stearic acid amide, palmitic acid amide, methylene bis stearic acid amide, ethylene bis stearic acid amide, oleic acid amide, palmitic acid amide and other fatty acid amide waxes, lower alcohol esters of fatty acids, polyol esters of fatty acids, fatty acid polyglycol esters and other ester waxes, cetyl alcohol, stearyl alcohol and other alcohol waxes, metal soaps derived from fatty acids with carbon numbers of 12 to 30, etc. Among them, plant waxes and animal waxes are preferred, and lignite waxes are particularly preferred. However, the wax used is not particularly limited.
[0206] (Polyolefin resin)
[0207] The polyester resin composition may contain a polyolefin resin. The density of the polyolefin resin used is preferably 0.95 g / cm 3 the following.
[0208] The density of the polyolefin resin is more preferably 0.93 g / cm 3 Below, more preferably 0.92 g / cm 3 The lower limit is 0.90 g / cm2 based on the heat resistance and punching properties of the multilayer sheet.3 above.
[0209] In addition, the melt flow rate (MFR) of the polyolefin resin is preferably 0.1g / 10 minutes or more, more preferably 0.5g / 10 minutes or more, and further preferably 1g / minute or more. The upper limit is preferably 100g / 10 minutes or less based on the mechanical properties such as the impact resistance of the multilayer sheet. It should be noted that these densities and MFR are values obtained based on the method of JISK-6760-1981.
[0210] As the above-mentioned polyolefin resin, for example, high-density polyethylene, branched low-density polyethylene, linear low-density polyethylene, ultra-low-density polyethylene, polypropylene, ethylene-propylene copolymer, maleic acid-modified polyethylene, vinyl acetate-ethylene copolymer, ethyl acrylate-ethylene copolymer, ethylene-propylene copolymer, glycidyl methacrylate-ethylene copolymer, glycidyl methacrylate-ethyl acrylate-ethylene copolymer, etc. can be cited. They can be used alone or in combination of two or more. It should be noted that in this specification, polyethylene resin is also referred to as "PE resin".
[0211] In addition to the polyolefin resin and inorganic fine particles, a crystal nucleating agent such as a PBT oligomer, an organic nucleating agent such as sodium benzoate or sodium stearate may be added to the polyester resin composition.
[0212] The polyester resin composition may contain an antioxidant. Examples of the antioxidant include phenolic antioxidants, phosphorus antioxidants, sulfur antioxidants, and amine antioxidants. Hindered phenolic antioxidants are particularly effective.
[0213] As such hindered phenol antioxidants, known substances can be used, and examples thereof include pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxy-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, benzyl)benzene, 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methyl-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy)-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, 1,3,5-tri(4-tert-butyl-3-hydroxy-2,6-dimethylbenzene)isophthalic acid, triethylene glycol-bis[3-(3-tert-butyl-5 -methyl-4-hydroxy-3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate), 1,6-hexanediol-bis[3-(3,3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), 2,2-thio-diethylene-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), octadecyl-3-(3,5
[0066] In some embodiments, the hindered phenol-based oxidation stabilizer may be bonded to the polyester.
[0214] When manufacturing a polyester resin composition compounded with the aforementioned polyolefin resin and the like, in addition to a common method such as a method of directly adding the aforementioned polyolefin resin to the aforementioned polyester resin so that the content thereof is within the aforementioned range and melt-kneading, or a method of adding the polyolefin resin as a masterbatch and melt-kneading, the aforementioned polyolefin resin can also be mixed in as a powder or granular form during the manufacturing stage of the aforementioned polyester resin, for example, during melt polycondensation, immediately after melt polycondensation, immediately after precrystallization, during solid phase polymerization, immediately after solid phase polymerization, or in a process from the end of the manufacturing stage to the film-forming stage.
[0215] As a method of blending inorganic fine particles, antioxidants, etc., a method of adding them as a masterbatch and performing melt kneading is preferred. In this case, it is preferred to blend them in a polyester resin masterbatch blended with the above-mentioned polyolefin resin.
[0216] Melt kneading can be carried out by any conventionally known method, and can be carried out with good productivity using a single-screw and / or twin-screw extruder. When melt kneading is carried out using an extruder, the temperature is usually set to a temperature above the melting point, preferably 270 to 300°C, more preferably 275 to 280°C.
[0217] The polyester resin composition used in the polyester sheet for container can be mixed with other additives, such as known ultraviolet absorbers, oxygen absorbers, oxygen capture agents, epoxy compounds, isocyanate compounds, carbodiimide compounds and other reactive group compounds, metal deactivators, antibacterial agents, fluorescent whitening agents, fillers, lubricants added from the outside, lubricants precipitated internally during the reaction, release agents, nucleating agents, stabilizers, antistatic agents, pigments and other additives, various polymers as required. As polymers, for example, polyamide polymers, polyester elastomers and other polyester polymers, polystyrene polymers, polyacrylic acid polymers, etc. can be cited. They can be added during melt mixing and melt molding, or they can be added to the raw resin in advance.
[0218] Furthermore, the polyester resin composition may also contain an ultraviolet shielding resin, a heat-resistant resin, a recycled product from used polyethylene terephthalate bottles, and the like at an appropriate ratio.
[0219] The polyester sheet for container is formed of a single layer or multiple layers using the aforementioned polyester resin. The multiple layers are formed of polyester resin compositions having different compositions. In this case, only the type or content of the additives may be different. When formed of multiple layers, when a container is formed and the contents are placed in the container, the layer on the side to be the contents is the inner layer, and the layer on the opposite side is the surface layer.
[0220] The intrinsic viscosity of the polyester sheet for containers is preferably in the range of 0.70 to 2.00 dl / g, more preferably 0.75 to 1.50 dl / g, and further preferably 0.80 to 1.30 dl / g. When the intrinsic viscosity is too low, the mechanical properties of the obtained polyester sheet, such as impact resistance and pinhole resistance, may be deteriorated. Moreover, when the intrinsic viscosity is too high, the resin temperature during melting by the extruder becomes high, and the thermal decomposition may become rapid, and the content of free low molecular weight compounds such as acetaldehyde that affect the flavor retention may increase. Moreover, when the polyester resin for obtaining such a high viscosity polyester sheet is produced, it is only possible to use an uneconomical production method, which becomes costly and disadvantageous from the viewpoint of economic efficiency.
[0221] (wax)
[0222] In the polyester sheet for containers, it is preferred that the surface layer contain wax, and it is more preferred that the inner layer also contain wax.
[0223] The wax content in each layer is preferably 0.01% by weight or more, more preferably 0.05% by weight or more, and the upper limit is preferably 1.0% by weight or less, more preferably 0.5% by weight or less.
[0224] (Polyolefin resin)
[0225] The total amount of the polyolefin resin used in the polyester sheet is preferably 0.5% by weight or more, more preferably 1% by weight or more, further preferably 1.5% by weight or more, and particularly preferably 2% by weight or more. In addition, the upper limit is preferably 10% by weight or less, more preferably 8% by weight or less, and further preferably 6% by weight or less.
[0226] When the polyester sheet is formed of multiple layers, the lower limit of the total amount of polyolefin resin used in the polyester sheet is preferably 0.5% by weight or more, more preferably 1% by weight or more, further preferably 1.5% by weight or more, and particularly preferably 2% by weight or more for the inner layer. In addition, the upper limit is preferably 10% by weight or less, more preferably 8% by weight or less, and further preferably 6% by weight or less.
[0227] By making the amount of polyolefin resin the amount of the above range, the container obtained has excellent impact resistance, and excellent punching property when punching after forming into a sheet, and a beautiful appearance is obtained. That is, if the amount of polyolefin resin is too much, its punching property is easy to deteriorate, and it can be seen that insufficiently cut sheet fragments remain on the cut surface, which sometimes becomes a cause of poor appearance. In addition, it is easy to produce a peculiar odor of polyolefin resin. In addition, when it is too little, the crystallization rate of the obtained polyester sheet is easy to slow down, the heat resistance of the polyester sheet is reduced, and the impact resistance improvement effect is not easy to become sufficient.
[0228] Preferably, the surface layer does not substantially contain a polyolefin resin. Here, “substantially free” means that it may be contained in an extremely small amount to a degree that does not cause mold contamination, but does not necessarily mean that it is not contained at all. It varies depending on the type of polyolefin, and is more preferably 0.2% by weight or less, further preferably 0.1% by weight or less, and particularly preferably 0.05% by weight or less.
[0229] (Inorganic particles)
[0230] The content of inorganic fine particles in the polyester sheet for containers is preferably 0.1 to 10% by weight, more preferably 0.3 to 7% by weight, and particularly preferably 0.5 to 5% by weight in each layer. When the amount of the compounding is too small, it is sometimes necessary to increase the heat treatment temperature for crystallization or extend the heat treatment time without changing the crystallization rate of the unmodified polyester, which makes it difficult to remove from the mold or sometimes reduces productivity. On the other hand, when the amount of the compounding is too large, there is a tendency that the degree of crystallinity during thermoforming becomes higher and the impact resistance decreases, and when the amount is above a certain level, no significant improvement in the crystallization rate is observed. Furthermore, the shaping property during thermoforming deteriorates and the molding condition range becomes narrower, so the compounding amount is preferably suppressed to 10% by weight or less.
[0231] The content of the crystal nucleating agent in the polyester sheet for containers is preferably 5% by weight or less in each layer, and is appropriately set according to the type of the nucleating agent. In order to obtain the effect of its addition, it is preferably 0.01% by weight or more in at least the inner layer of the polyester sheet for containers. It should be noted that sometimes the process includes: reusing the two ends of the sheet cut off during sheet production in the inner layer. In this case, when the crystal nucleating agent present in the layer other than the inner layer is mixed into the inner layer, the amount of the mixed nucleating agent can also be included in the above-mentioned addition amount.
[0232] (Antioxidant)
[0233] In addition, the content of the antioxidant in the polyester sheet for containers is preferably 0.005% by weight or more, more preferably 0.01% by weight or more in each layer, and preferably 3.0% by weight or less, more preferably 2.0% by weight or less. When the compounding amount is too small, the thermal oxidation prevention ability is small, and the impact strength of the container is sometimes reduced depending on the use of the container and the heat treatment conditions. In addition, when the compounding amount is too large, the coloring of the obtained container becomes rapid, or a bad smell is generated, and the aroma retention is deteriorated, which sometimes becomes a problem.
[0234] In the surface layer, resins other than the polyester resin and the polyolefin resin may be used as required within a range that does not impair the properties of the container. Specifically, the amount of the resin other than the polyester resin and the polyolefin resin is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, further preferably 5 parts by weight or less, and particularly preferably 2 parts by weight or less, relative to 100 parts by weight of the polyester resin.
[0235] The surface layer constituting the polyester sheet for a container is preferably formed of a polyester resin composition containing polyester resin and inorganic particles or containing them and wax and substantially containing no polyolefin resin, and the inner layer is preferably formed of a polyester resin and inorganic particles and polyolefin resin or containing them and wax.
[0236] In the inner layer, it is preferred that no resin other than the polyester resin and the polyolefin resin be used, but as required, resins other than the polyester resin and the polyolefin resin may be used within a range that does not impair the characteristics of the container. Specifically, the amount of the resin other than the polyester resin and the polyolefin resin used is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, further preferably 5 parts by weight or less, and particularly preferably 2 parts by weight or less, relative to 100 parts by weight of the polyester resin.
[0237] The polyester sheet for containers can use a polyester resin having a fine flake content of preferably 10 ppm or more, more preferably 30 ppm or more, further preferably 50 ppm or more in at least the surface layer of the polyester resin composition, and preferably 10000 ppm or less, more preferably 7000 ppm or less, further preferably 5000 ppm or less.
[0238] When the content of fine flakes in the polyester sheet for container is 10ppm or more, the crystallization speed during sheet molding is not easy to slow down, the crystallinity of the sheet is easy to increase under normal molding conditions, and polyester oligomers, polyolefin oligomers, etc. are not easy to adhere to the high-temperature molding mold, and are not easy to contaminate the mold. It is also easy to maintain the fragrance of the content. In addition, when the content of fine flakes is less than 10000ppm, the crystallization speed does not become excessively fast, and the deep drawing formability is not easy to deteriorate when the container is molded by vacuum molding, etc., and it is easy to mold into a conventional shape and is not easy to break. Furthermore, when mixed with polyolefin resin for molding, the fine flakes are not easy to segregate, and unevenness is not easy to occur in the compounding amount of polyolefin resin.
[0239] (Cyclic trimer)
[0240] In addition, the content of cyclic trimers contained in the polyester sheet for containers is preferably 0.70 wt% or less, more preferably 0.60 wt% or less, and further preferably 0.50 wt% or less. When the content of cyclic trimers in the polyester sheet is too high, when the polyester sheet is heat-formed into a container or the like by a vacuum forming machine in a continuous production method, oligomers from the polyester resin and the polyolefin resin tend to gradually adhere to and accumulate on the heating mold, resulting in poor demolding properties between the heating mold and the polyester sheet, or poor gloss on the inner surface of the container, which is likely to become a problem. In addition, depending on the type of the content, the taste and smell are affected, which sometimes becomes a problem. The lower limit of the content of cyclic trimers contained in the polyester sheet is not particularly limited, but is preferably 0.10 wt% or more, and more preferably 0.20 wt% or more, from the perspective of productivity and the like.
[0241] A polyester sheet having a cyclic trimer content of 0.70 wt % or less can be obtained, for example, by using a polyester resin having a cyclic trimer content of 0.68 wt % or less and maintaining the resin temperature at about 270 to 295° C. during film formation, or by subjecting the polyester resin to a contact treatment at 20 to 180° C. in water or water vapor to deactivate a residual polycondensation catalyst, or by deactivating the catalyst with a phosphorus compound.
[0242] The heat shrinkage of the polyester sheet for containers is preferably 0.1 to 8%, more preferably 0.2 to 6%. In order to obtain a polyester sheet with a heat shrinkage that is too low (e.g., less than 0.1%), non-productive conditions must be used, which is economically disadvantageous. If the heat shrinkage is too large, the shape of the container will be deteriorated when it is molded, and a satisfactory container shape cannot be obtained, or the heat seal may become easily peeled off.
[0243] When the heating method in the preheating process of the polyester sheet for container molding is non-contact heating such as far infrared heating, it is preferably 2% or more, more preferably 3% or more. And the upper limit is preferably 8% or less, more preferably 6% or less. If the heat shrinkage rate is too low (for example, less than 2%), the sheet droops during the preheating process of the sheet when molding into a container, and the workability may be significantly deteriorated. If it is too large, the same problem as above may occur.
[0244] As a method for adjusting the heat shrinkage rate of the polyester sheet for containers to 0.1 to 8%, the heat shrinkage rate can be adjusted by, for example, adjusting the pressure applied to the sheet between the touch roll and the cooling roll during sheet production, the temperature of the touch roll and the cooling roll, the resin discharge amount of the polyester resin composition from the extruder, and the sheet take-up rate, etc. Generally, the heat shrinkage rate can be reduced by adjusting the residual strain to be small.
[0245] For example, as a general tendency, when the winding rate of the sheet is too high relative to the discharge amount of the polyester resin composition, the heat shrinkage rate of the obtained sheet becomes larger than the above range, and when the winding rate is too low, the heat shrinkage rate also becomes smaller than the above range. In addition, when the pressure between the touch roll and the cooling roll is large, the heat shrinkage rate also tends to become larger.
[0246] The above conditions also depend greatly on the characteristics of the polyester resin composition used, such as polymerization degree, copolymer components, blending ratio, etc. Therefore, the conditions most suitable for the base must be appropriately optimized according to the resin used and the machine for sheet molding.
[0247] The polyester resin composition is dried as needed to remove the water content. The resin composition from which the water has been removed is then melted in a single screw extruder or a twin screw extruder, extruded from a multi-layer T-die installed at the outlet of the extruder onto a casting drum, and the sheet is quenched and solidified to obtain a polyester sheet.
[0248] The thickness of the polyester sheet for containers is preferably in the range of 100 to 1000 μm, more preferably 150 to 800 μm.
[0249] In addition, the scraps generated during film formation can be reused as a raw material for the layer that does not come into direct contact with food.
[0250] The polyester sheet for containers can have high heat resistance of 200° C. or more by crystallization. Heating crystallization can be performed by a method using hot air, a method using infrared irradiation, a method using a mold, a method using a belt heater, etc., and the method can be freely selected according to the molding method, etc.
[0251] Polyester sheets for containers are processed into containers such as trays through pressure, vacuum, compression, etc.
[0252] The polyester container can be filled with food, sealed with the lid using the heat sealant, and then sterilized by a known retort sterilization process, or heated in a microwave oven or an electric oven.
[0253] By making the resin on the container side and the resin on the cap side the same composition or using compositions that can be mixed while maintaining transparency (hereinafter, resins of similar composition) when melt-mixing the cap material and the container, a single-material packaging material with excellent recyclability can be obtained.
[0254] (Industrial Applicability)
[0255] The biaxially oriented polyester film of the present invention has unprecedented excellent properties in terms of impact strength and heat resistance, and therefore can be preferably used as a cover material for packaging bags and containers.
[0256] Furthermore, it is also suitable for applications used at high temperatures, such as insulating films for capacitors and motors, and barrier films for inorganic oxides. In addition, coating and printing processing at high temperatures are possible using coating agents, inks, laminating adhesives, etc. that were not easy to use in the past, and further efficiency of production can be expected.
[0257] Example
[0258] Next, the effects of the present invention will be described using examples and comparative examples. The thin film of the invention is not limited to the method specifically disclosed below as long as it is within the scope of the technical concept of the present application.
[0259] First, the evaluation method of the characteristic values used in the present invention is shown below.
[0260] [Evaluation method]
[0261] (1) Polyester resin composition
[0262] The polyester resin was dissolved in deuterated chloroform and analyzed by 1H-NMR using a nuclear magnetic resonance analyzer (NMR) Gemini-200 manufactured by Varian, and the content (mol %) of each component was determined from the integrated ratio.
[0263] (2) Intrinsic viscosity (IV) of polyester
[0264] After drying the polyester resin, it was dissolved in a mixed solvent of p-chlorophenol / tetrachloroethane = 75 / 25 (weight ratio). The flow time of a solution with a concentration of 0.4 (g / dl) at 30°C and the flow time of only the solvent were measured using an Ubbelohde viscometer, and the intrinsic viscosity was calculated from these time ratios using the Huggins formula, assuming that the Huggins constant was 0.38.
[0265] (3) Melting point (Tm) and glass transition temperature (Tg) of polyester resin
[0266] The measurement was conducted in accordance with JIS K 7121-2012 "Transition temperature of plastics". Using a differential scanning calorimeter (manufactured by Seiko Instruments Inc., EXSTAR6000), 10 mg of a resin sample was heated at 10°C / min from 25°C to the melting point of the resin + 30°C, and the position of the peak of the heat of crystal fusion was taken as the melting point (Tm, unit: °C).
[0267] The temperature at the point where a straight line extending from each base line at an equal distance in the vertical axis direction intersects a curve of the step-like change portion of the glass transition was taken as the glass transition temperature (Tg, unit: °C).
[0268] (4) Heating crystallization temperature (Tc) of polyester resin
[0269] The measurement was carried out in accordance with JIS K 7121-2012 "Method for determining transition temperature of plastics". A 10 mg polyester resin sample quenched from a molten state was heated at 5°C / min from 25°C to the melting point of the resin + 30°C using a differential scanning calorimeter (manufactured by Seiko Instruments Inc., EXSTAR6000), and a curve (DSC curve) was obtained with heat flow (Heat Flow / mW) plotted on the vertical axis and temperature plotted on the horizontal axis. The top of the crystallization peak visible between the glass transition temperature (Tg) and the melting point (Tm) was taken as the temperature (Tc).
[0270] When no clear crystallization peak was observed in the above method, the temperature increase rate was set to 1° C. / min, and the temperature increase crystallization temperature (Tc) was determined from the obtained DSC curve.
[0271] (5) Half-crystallization time of polyester resin
[0272] The polyester resin was evaluated by isothermal crystallization treatment using a differential scanning calorimeter (EXSTR6000 manufactured by SII Nanotechnology Inc.) and by the Avrami index in the Avrami formula represented by the following formula (3) and the half crystallization time of the crystallization rate constant.
[0273] The isothermal crystallization treatment is as follows: the temperature is raised from room temperature to a temperature 35°C higher than the melting point of each resin at a rate of 10°C / min, maintained for 3 minutes, then cooled to a specified temperature at a rate of 50°C / min, maintained for a specified isothermal holding time, and then rapidly cooled in liquid nitrogen.
[0274] The specified temperature refers to any temperature that suits the resin from 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and 190°C, and at each isothermal holding temperature, samples are obtained that are maintained for isothermal holding times of 10 minutes, 50 minutes, 100 minutes, and 200 minutes.
[0275] The sample that has undergone isothermal crystallization treatment is heated again from room temperature to a temperature 30°C higher than the melting point of the polyester resin at a rate of 10°C / min. Based on the DSC curve at this time, the ratio X(t) of the heat involved in crystal melting of the sample that has undergone isothermal crystallization treatment to the theoretical heat of fusion when the sample is completely crystallized after t (minutes) treatment is calculated.
[0276] The isothermal holding time was t (minutes), X(t) and the Avrami formula shown in formula (1), and n as the Avrami index and K as the crystallization rate constant were determined.
[0277] The half crystallization time T(1 / 2) was calculated from n, which is the Avrami index, and K, which is the crystallization rate constant, using the formula (3).
[0278] Compare the half-crystallization times at various temperatures t (any temperature that suits the resin from 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and 190°C), take the temperature with the shortest time as the crystallization temperature, and take the half-crystallization time at this time as the half-crystallization time of the corresponding polyester resin.
[0279] log(-ln[1-X(t)])=nlogt+logK ···Formula (2)
[0280] T 1 / 2 =(ln2 / K) 1 / n Formula (3)
[0281] (6) Refractive index and plane orientation coefficient of the film
[0282] The refractive index was measured in accordance with JIS K 7142. The refractive index was measured using an Abbe refractometer under NaD rays at a temperature of 23°C. The mount liquid used was diiodomethane, and the refractive index in the length direction (Nx), the width direction (Ny), and the thickness direction (Nz) were measured. The measurement was performed at the center of the film.
[0283] The plane orientation coefficient (ΔP) is calculated using the formula [(Nx+Ny) / 2]-Nz.
[0284] In addition, the birefringence (ΔNxy) is calculated using the formula Nx-Ny.
[0285] When another layer is provided on one surface, the surface on the other side is measured three times, and the average value thereof is determined.
[0286] (7) Stretchability
[0287] In the following Examples and Comparative Examples, film formation was continued for 20 minutes, and the number of breaks during the process was measured.
[0288] ◎: No breakage
[0289] ○: Fracture occurred, but the film can be collected
[0290] ×: Frequent breakage, unable to collect film
[0291] (8) Density
[0292] The density was measured by the D method in accordance with JIS K 7112 using a density gradient tube.
[0293] The biaxially oriented polyester film was cut into a size of 5 mm in the width direction and 5 mm in the length direction to prepare a sample, and the measurement was performed at 25°C.
[0294] (9) 150°C heating shrinkage of the film in the longitudinal direction (%)
[0295] The measurement is based on JIS C 2318-1997 5.3.4 (dimensional change). A rectangular sample with a size of 10 mm in the width direction of the film and 190 mm in the length direction of the film is marked with marking lines at intervals of 150 mm from one short side along the long side and parallel to the short side, and the intervals (A) between the marking lines are measured.
[0296] Next, the film was placed in an oven in an atmosphere of 150° C., and heat-treated at 150° C.±3° C. for 30 minutes without a load, and then the interval (B) between the marking lines was measured.
[0297] Each heat shrinkage ratio (%) was calculated according to the following formula, and the average value thereof was defined as the 150° C. heating shrinkage ratio in the longitudinal direction.
[0298] Thermal shrinkage (%) = (AB) / A×100···Formula (4)
[0299] The polylactic acid film was placed in an oven in an atmosphere of 120° C. and heat treated at 120° C.±3° C. for 30 minutes without a load to evaluate the heat shrinkage at 120° C.
[0300] (10) Thermal shrinkage stress in the longitudinal direction of the film (MPa)
[0301] The measurement was performed using a TMA / SS6100 thermomechanical analyzer manufactured by Seiko Instruments Inc. A rectangular sample having a size of 2 mm in the width direction of the film and 30 mm in the length direction of the film was cut. Then, the sample was placed on the device so that the distance between the chucks was 20 mm.
[0302] Next, select the assembly L control mode, raise the temperature from room temperature to 200°C at a rate of 20°C / min, and read the maximum value of the thermal shrinkage stress curve at a temperature above the glass transition temperature (Tg) of the polyester resin from the obtained thermal shrinkage stress curve as the thermal shrinkage stress in the longitudinal direction of the film.
[0303] (11) Impact strength (J / 12μm)
[0304] The impact strength was measured using an impact strength measuring device (product name: film impact tester, manufacturing number T-84-3) manufactured by Toyo Seiki Seisaku-sho Co., Ltd. A rectangular sample having a length of 100 mm in the width direction of the film and a length of 100 mm in the length direction of the film was cut.
[0305] Next, a sample is placed on the device, and the film's strength against impact punching is measured at 23°C using an impact sphere with a diameter of 1 / 2 inch. The strength per 12 μm thickness is converted into impact strength, and the unit is J / 12 μm.
[0306] In addition, the thickness correction method of impact strength is as follows.
[0307] (Impact strength) = (measured value) / (thickness of the measurement sample) × 12 ... Formula (5)
[0308] (12) Printing suitability
[0309] Gravure ink (RAMIACE 61 white two-component type, manufactured by Toyo Ink Co., Ltd.) was gravure-printed on the biaxially oriented polyester film used in Examples and Comparative Examples and dried to form a printed ink layer.
[0310] In this step, the state of the film was observed and evaluated based on the following criteria.
[0311] In Examples 2-1 to 5, evaluation was performed on the substrate layer side.
[0312] ◎: No wrinkles or bends, excellent film flatness
[0313] ○: Slight wrinkles and bends are visible, and the film has good flatness
[0314] ×: Wrinkles occurred and the flatness was poor
[0315] (13) Processing suitability
[0316] A polyester urethane two-component curing adhesive ("Takelac A525S" and "Takenate A50" manufactured by Mitsui Chemicals, Inc.) was coated on the biaxially oriented polyester film used in the examples and comparative examples so that the thickness after drying became 3 μm, and then a linear low-density polyethylene film (L-LDPE film: manufactured by Toyobo, L4102) with a thickness of 40 μm was adhered so that the length directions were aligned with each other, and aged for 3 days at 40°C to form a laminate.
[0317] The laminate was cut into rectangular samples of 70 mm in the width direction and 105 mm in the length direction of the film, and two sheets of the linear low-density polyethylene film side of the laminate were overlapped inside to evaluate the appearance when heat-sealed at 150°C. The polylactic acid film was heat-sealed at 125°C.
[0318] ◎: No wrinkles, excellent appearance
[0319] ○: Slightly visible wrinkles, but good appearance
[0320] ×: Wrinkles are visible and the appearance is poor
[0321] (14) Bag breaking characteristics (bag drop test)
[0322] The laminated film was heat-sealed at a sealing temperature of 160°C and a sealing width of 1.0 cm to prepare 10 bags of 150 mm×150 mm filled with water, and then retorted at 125°C for 30 minutes. The bags were repeatedly dropped from a height of 1 m in an environment of 25°C, and the average number of bag drops until the bags broke or leaked was used for evaluation. The polylactic acid film was heat-sealed at 125°C.
[0323] ◎: The number of drops until the bag breaks or leaks is 5 or more.
[0324] 0: The number of drops until the bag breaks or leaks is 2 or more.
[0325] ×: The number of drops until the bag breaks or leaks is 1 or less.
[0326] Hereinafter, the present invention will be described based on examples, but the present invention is not limited to these examples.
[0327] The types and contents of the polyester resins used in Examples and Comparative Examples are described.
[0328] (Polyester resin-A)
[0329] Polyethylene terephthalate / ethylene isophthalate (10 mol% of repeating units of ethylene isophthalate, IV = 0.95)
[0330] In a reaction apparatus equipped with an inlet, a thermometer, a pressure gauge, a distillation pipe with a distillation tower, and stirring blades, 88 parts by weight of terephthalic acid, 12 parts by weight of isophthalic acid, 82 parts by weight of ethylene glycol (molar ratio of ethylene glycol / total acid components = 2.2), 0.05 mol% of germanium oxide in terms of Ge element and 0.05 mol% of magnesium acetate in terms of Mg element relative to the acid components were charged, and nitrogen was introduced while stirring, and the pressure in the system was maintained at 0.3 MPa, while the generated water was distilled out of the system at a temperature of 230° C. to 250° C., and an esterification reaction was carried out. After the reaction was completed, 0.04 mol% of trimethyl phosphate in terms of P was added at 250° C., and the temperature was raised while the pressure was gradually reduced, and a polycondensation reaction was carried out at 275° C. and a vacuum of 1.0 hPa or less to obtain a polyester. The polyester was then heat treated at 200°C and 1.0 hPa in vacuum for 19 hours, and the intrinsic viscosity of the obtained polyester was 0.95 (dl / g). The melting point of the obtained polyester was 230°C, the glass transition temperature was 73°C, the heating crystallization temperature was 158°C, and the half crystallization time was 200 minutes.
[0331] (Polyester resin-B)
[0332] Polyethylene terephthalate / ethylene isophthalate (10 mol% of repeating units of ethylene isophthalate, IV = 0.70)
[0333] In a reaction apparatus equipped with an inlet, a thermometer, a pressure gauge, a distillation pipe with a distillation tower, and stirring blades, 88 parts by weight of terephthalic acid, 12 parts by weight of isophthalic acid, 82 parts by weight of ethylene glycol (molar ratio of ethylene glycol / total acid components = 2.2), 0.05 mol% of germanium oxide in terms of Ge element and 0.05 mol% of magnesium acetate in terms of Mg element relative to the acid components were charged, and nitrogen was introduced while stirring, and the pressure in the system was maintained at 0.3 MPa, while the generated water was distilled out of the system at a temperature of 230° C. to 250° C., and an esterification reaction was carried out. After the reaction was completed, 0.04 mol% of trimethyl phosphate in terms of P was added at 250° C., and the temperature was raised while the pressure was gradually reduced, and a polycondensation reaction was carried out at 275° C. and a vacuum of 1.0 hPa or less to obtain a polyester. The polyester was then heat treated at 200°C and 1.0 hPa in vacuum for 13 hours, and the intrinsic viscosity of the obtained polyester was 0.70 (dl / g). The melting point of the obtained polyester was 230°C, the glass transition temperature was 73°C, the heating crystallization temperature was 155°C, and the half crystallization time was 100 minutes.
[0334] (Polyester resin-C)
[0335] Polyethylene terephthalate / ethylene isophthalate (5 mol% of repeating units of ethylene isophthalate, IV = 0.95)
[0336] In a reaction apparatus equipped with an inlet, a thermometer, a pressure gauge, a distillation pipe with a distillation tower, and stirring blades, 94 parts by weight of terephthalic acid, 6 parts by weight of isophthalic acid, 82 parts by weight of ethylene glycol (molar ratio of ethylene glycol / total acid components = 2.2), 0.06 mol% of antimony trioxide in terms of Sb element and 0.05 mol% of magnesium acetate in terms of Mg element relative to the acid components were charged, and nitrogen was introduced while stirring, and the pressure in the system was maintained at 0.3 MPa, while the generated water was distilled out of the system at a temperature of 230° C. to 250° C., and an esterification reaction was carried out. After the reaction was completed, 0.04 mol% of trimethyl phosphate in terms of P was added at 250° C., and the temperature was raised while the pressure was gradually reduced, and a polycondensation reaction was carried out at 275° C. and a vacuum of 1.0 hPa or less to obtain a polyester. Then, the polyester was heat treated at 200°C and 1.0 hPa vacuum for 19 hours, and the intrinsic viscosity of the obtained polyester was 0.95 (dl / g). The melting point of the obtained polyester was 240°C, the glass transition temperature was 76°C, the heating crystallization temperature was 140°C, and the half crystallization time was 50 minutes.
[0337] (Polyester resin-D)
[0338] Sebacic acid copolymerized polyethylene terephthalate resin (copolymerization ratio of the component derived from sebacic acid in the component derived from carboxylic acid is 10 mol%, IV=0.90)
[0339] In a reaction apparatus equipped with an inlet, a thermometer, a pressure gauge, a distillation pipe with a distillation tower, and stirring blades, 88 parts by weight of terephthalic acid, 12 parts by weight of sebacic acid, 82 parts by weight of ethylene glycol (molar ratio of ethylene glycol / total acid components = 2.2), 0.05 mol% of germanium oxide in terms of Ge element and 0.05 mol% of magnesium acetate in terms of Mg element relative to the acid components were charged, and nitrogen was introduced while stirring, and the pressure in the system was maintained at 0.3 MPa, while the generated water was distilled out of the system at a temperature of 230° C. to 250° C., and an esterification reaction was carried out. After the reaction was completed, 0.04 mol% of trimethyl phosphate in terms of P was added at 250° C., and the temperature was raised while the pressure was gradually reduced, and a polycondensation reaction was carried out at 275° C. and a vacuum of 1.0 hPa or less to obtain a polyester. The polyester was then heat treated at 195°C and 1.0 hPa in vacuum for 18 hours, and the intrinsic viscosity of the obtained polyester was 0.90 (dl / g). The melting point of the obtained polyester was 232°C, the glass transition temperature was 63°C, the heating crystallization temperature was 124°C, and the half crystallization time was 300 minutes.
[0340] (Polyester resin-E)
[0341] Sebacic acid copolymerized polyethylene terephthalate resin (copolymerization ratio of the component derived from sebacic acid in the component derived from carboxylic acid is 18 mol%, IV=0.75)
[0342] In a reaction apparatus equipped with an inlet, a thermometer, a pressure gauge, a distillation pipe with a distillation tower, and stirring blades, 80 parts by weight of terephthalic acid, 20 parts by weight of sebacic acid, 82 parts by weight of ethylene glycol (molar ratio of ethylene glycol / total acid components = 2.2), 0.05 mol% of germanium oxide in terms of Ge element and 0.05 mol% of magnesium acetate in terms of Mg element relative to the acid components were charged, and nitrogen was introduced while stirring, and the pressure in the system was maintained at 0.3 MPa, while the generated water was distilled out of the system at a temperature of 230° C. to 250° C., and an esterification reaction was carried out. After the reaction was completed, 0.04 mol% of trimethyl phosphate in terms of P was added at 250° C., and the temperature was raised while the pressure was gradually reduced, and a polycondensation reaction was carried out at 275° C. and a vacuum of 1.0 hPa or less to obtain a polyester. The polyester was then heat treated at 195°C and 1.0 hPa in vacuum for 15 hours, and the intrinsic viscosity of the obtained polyester was 0.75 (dl / g). The melting point of the obtained polyester was 205°C, the glass transition temperature was 45°C, the heating crystallization temperature was 142°C, and the half crystallization time was 700 minutes.
[0343] (Polyester resin-F)
[0344] Sebacic acid copolymerized polyethylene terephthalate / ethylene isophthalate (copolymerization ratio of the component derived from sebacic acid in the component derived from carboxylic acid is 5 mol%, repeating unit of ethylene isophthalate is 10 mol%, IV=0.95)
[0345] In a reaction apparatus equipped with an inlet, a thermometer, a pressure gauge, a distillation pipe with a distillation tower, and stirring blades, 82 parts by weight of terephthalic acid, 6 parts by weight of sebacic acid, 12 parts by weight of isophthalic acid, 82 parts by weight of ethylene glycol (molar ratio of ethylene glycol / total acid components = 2.2), 0.06 mol% of antimony trioxide in terms of Sb element and 0.05 mol% of magnesium acetate in terms of Mg element relative to the acid components were charged, and nitrogen was introduced while stirring, and the pressure in the system was maintained at 0.3 MPa, while the generated water was distilled out of the system at a temperature of 230° C. to 250° C., and an esterification reaction was carried out. After the reaction was completed, 0.04 mol% of trimethyl phosphate in terms of P was added at 250° C., and the temperature was raised while the pressure was gradually reduced, and a polycondensation reaction was carried out at 275° C. and a vacuum of 1.0 hPa or less to obtain a polyester.
[0346] The polyester was then heat treated at 200°C and 1.0 hPa in vacuum for 19 hours, and the intrinsic viscosity of the obtained polyester was 0.95 (dl / g). The melting point of the obtained polyester was 205°C, the glass transition temperature was 48°C, the heating crystallization temperature was 158°C, and the half crystallization time was 800 minutes.
[0347] (Polyester resin-G)
[0348] Polyethylene terephthalate / ethylene isophthalate (12 mol% of repeating units of ethylene isophthalate, IV = 0.65)
[0349] In a reaction apparatus equipped with an inlet, a thermometer, a pressure gauge, a distillation pipe with a distillation tower, and stirring blades, 86 parts by weight of terephthalic acid, 14 parts by weight of isophthalic acid, 82 parts by weight of ethylene glycol (molar ratio of ethylene glycol / total acid components = 2.2), 0.05 mol% of germanium oxide in terms of Ge element and 0.05 mol% of magnesium acetate in terms of Mg element relative to the acid components were charged, and nitrogen was introduced while stirring, and the pressure in the system was maintained at 0.3 MPa, while the generated water was distilled out of the system at a temperature of 230° C. to 250° C., and an esterification reaction was carried out. After the reaction was completed, 0.04 mol% of trimethyl phosphate in terms of P was added at 250° C., and the temperature was raised while the pressure was gradually reduced, and a polycondensation reaction was carried out at 275° C. and a vacuum of 1.0 hPa or less to obtain a polyester. The polyester was then heat treated at 200°C and 1.0 hPa in vacuum for 12 hours to obtain a polyester having an intrinsic viscosity of 0.65 (dl / g), a melting point of 229°C, a glass transition temperature of 73°C, and a crystallization half time of 100 minutes.
[0350] (Polyester resin-H)
[0351] Polyethylene terephthalate (IV=0.62): This polyester has an intrinsic viscosity of 0.62 (dl / g), a melting point of 256°C, a glass transition temperature of 78°C, a heating crystallization temperature of 130°C, and a half crystallization time of 1 minute.
[0352] (Polyester resin-I)
[0353] Polylactic acid resin (Luminy(R) PAL L175 manufactured by Total Corbion Co., Ltd.). The polyester had a melt flow index of 8 (g / 10 minutes) at 210°C / 2.16kg, a melting point of 173°C, a glass transition temperature of 55°C, a heating crystallization temperature of 135°C, a half crystallization time of 4 minutes, and an L-lactic acid ratio of 99.5%.
[0354] (Polyester Resin-J)
[0355] Polylactic acid resin (Luminy(R) PAL LX175 manufactured by Total Corbion Co., Ltd.) The polyester had a melt flow index of 8 (g / 10 minutes) at 210°C / 2.16kg, a melting point of 150°C, a glass transition temperature of 53°C, a heating crystallization temperature of 121°C, a half crystallization time of 330 minutes, and an L-lactic acid ratio of 96%.
[0356] (Polyester resin-K)
[0357] Polyethylene terephthalate copolymer polyester resin (Vylon RV30P manufactured by Toyobo Co., Ltd.) The melting point of this polyester resin is 130°C and Tg is -30°C.
[0358] (Polyester resin-L)
[0359] Adipic acid-copolybutylene terephthalate resin (manufactured by BASF Corporation, Ecoflex) This polyester resin has a melting point of 210°C and a Tg of 25°C.
[0360] (Polyester resin-M)
[0361] Polybutylene succinate resin (FZ91PM manufactured by Mitsubishi Chemical Corporation). The melt flow rate of this polyester is 5 g / 10 min, Tm is 115° C., and Tg is −22° C. This resin is produced from plant-derived raw materials.
[0362] (Example 1)
[0363] After the polyester resin-A was dried under reduced pressure (1Torr) at 135°C for 6 hours, it was supplied to the extruder. When the resin temperature of the melting section, kneading section, piping, gear pump, and filter of the extruder was 280°C, and the subsequent piping and T-die head was 275°C, the raw material supplied to the extruder was melt-extruded from the T-die head into a sheet, and cooled on a cooling roller at 40°C to obtain an amorphous sheet. The sheet was stretched to 3.5 times at 105°C in the length direction. Then, the film stretched in the length direction was introduced into a tenter, preheated at 140°C, stretched 6.0 times in the width direction at 150°C, and then heat treated at 215°C, and subjected to a 7% relaxation treatment to obtain a biaxially stretched polyester film with a thickness of 12μm. The obtained film has good stretchability, and is also excellent in heat resistance and impact strength.
[0364] (Example 2)
[0365] An amorphous sheet was obtained in the same manner as in Example 1 except that the polyester resin-B was used.
[0366] The sheet was stretched to 3.0 times in the longitudinal direction at 105°C. Then, the film stretched in the longitudinal direction was heated at 100°C for 1 second, introduced into a tenter, preheated at 140°C, stretched 6.0 times in the width direction at 150°C, heat treated at 210°C, and relaxed by 10% to obtain a biaxially stretched polyester film having a thickness of 12 μm. The obtained film had good stretchability, excellent heat resistance and excellent impact strength.
[0367] (Example 3)
[0368] An amorphous sheet was obtained in the same manner as in Example 1 except that the polyester resin-C was used.
[0369] The sheet was stretched to 3.0 times in the longitudinal direction at 105°C. Then, the film stretched in the longitudinal direction was heated at 100°C for 1 second, introduced into a tenter, preheated at 110°C, stretched 4.5 times in the width direction at 120°C, heat treated at 210°C, and relaxed by 10% to obtain a biaxially stretched polyester film having a thickness of 15 μm. The obtained film had good stretchability, and was also excellent in heat resistance and impact strength.
[0370] (Example 4)
[0371] An amorphous sheet was obtained in the same manner as in Example 1 except that the polyester resin-D was used.
[0372] The sheet was stretched to 3.0 times in the longitudinal direction at 80°C. Then, the film stretched in the longitudinal direction was introduced into a tenter, preheated at 130°C, stretched 6.0 times in the width direction at 140°C, heat treated at 200°C, and relaxed by 7% to obtain a biaxially stretched polyester film having a thickness of 16 μm. The obtained film had good stretchability, excellent heat resistance and excellent impact strength.
[0373] (Example 5)
[0374] An amorphous sheet was obtained in the same manner as in Example 1 except that polyester resin-E was used.
[0375] The sheet was stretched to 3.5 times in the longitudinal direction at 70°C. Then, the film stretched in the longitudinal direction was heated at 100°C for 1 second, introduced into a tenter, preheated at 90°C, stretched 6.0 times in the width direction at 100°C, heat treated at 190°C, and relaxed by 7% to obtain a biaxially stretched polyester film having a thickness of 12 μm. The obtained film had good stretchability, and was also excellent in heat resistance and impact strength.
[0376] (Example 6)
[0377] An amorphous sheet was obtained in the same manner as in Example 1 except that polyester resin-F was used.
[0378] The sheet was stretched to 3.0 times in the longitudinal direction at 60°C. Then, the film stretched in the longitudinal direction was introduced into a tenter, preheated at 140°C, stretched 7.5 times in the width direction at 150°C, heat treated at 190°C, and relaxed by 12% to obtain a biaxially stretched polyester film having a thickness of 15 μm. The obtained film had good stretchability, excellent heat resistance and excellent impact strength.
[0379] (Example 7)
[0380] An amorphous sheet was obtained in the same manner as in Example 1 except that the polyester resin-B was used.
[0381] The sheet was stretched to 3.5 times in the longitudinal direction at 105°C. Then, the film stretched in the longitudinal direction was introduced into a tenter, preheated at 160°C, stretched 6.0 times in the width direction at 170°C, heat treated at 200°C, and relaxed by 10% to obtain a biaxially stretched polyester film having a thickness of 15 μm. The obtained film had good stretchability, and was also excellent in heat resistance and impact strength.
[0382] (Example 8)
[0383] Use polyester resin-I, dry under reduced pressure (1Torr) at 125°C for 6 hours, and then supply it to the extruder. When the resin temperature of the melting part, mixing part, piping, gear pump, and filter of the extruder is 220°C, and the subsequent piping and T-die are 220°C, the raw material supplied to the extruder is melt-extruded from the T-die into a sheet, and cooled on a cooling roller at 40°C to obtain an amorphous sheet. The sheet is stretched to 3.5 times in the length direction at 85°C. Then, the film stretched in the length direction is introduced into a tenter, preheated at 140°C, stretched 6.0 times in the width direction at 150°C, heat treated at 165°C, and subjected to 10% relaxation treatment to obtain a biaxially stretched polyester film with a thickness of 12μm. The obtained film has good stretchability, and is also excellent in heat resistance and impact strength.
[0384] (Example 9)
[0385] Polyester resin-J was used, and after being dried under reduced pressure (1Torr) at 125°C for 6 hours, it was supplied to the extruder. When the resin temperature of the melting section, mixing section, piping, gear pump, and filter of the extruder was 220°C, and the subsequent piping and T-die were 220°C, the raw material supplied to the extruder was melt-extruded from the T-die into a sheet, and cooled on a cooling roller at 40°C to obtain an amorphous sheet. The sheet was stretched to 4.5 times in the length direction at 85°C. Then, the film stretched in the length direction was introduced into a tenter, preheated at 135°C, stretched 6.0 times in the width direction at 140°C, heat treated at 140°C, and subjected to 10% relaxation treatment to obtain a biaxially stretched polyester film with a thickness of 12μm. The obtained film has good stretchability, and is also excellent in heat resistance and impact strength.
[0386] (Comparative Example 1)
[0387] An amorphous sheet was obtained in the same manner as in Example 1 using the polyester resin-A.
[0388] The sheet was stretched to 3.0 times in the longitudinal direction at 105°C. Then, the film stretched in the longitudinal direction was introduced into a tenter, preheated at 90°C, stretched 4.0 times in the width direction at 100°C, heat treated at 200°C, and relaxed by 5% to obtain a biaxially stretched polyester film with a thickness of 20 μm. The obtained film had good stretchability but poor heat resistance.
[0389] (Comparative Example 2)
[0390] An amorphous sheet was obtained in the same manner as in Example 1 using polyester resin-E.
[0391] The sheet was stretched to 3.0 times in the longitudinal direction at 70°C. Then, the film stretched in the longitudinal direction was introduced into a tenter, preheated at 65°C, stretched 4.0 times in the width direction at 70°C, heat treated at 170°C, and relaxed by 5% to obtain a biaxially stretched polyester film with a thickness of 20 μm. The obtained film had good stretchability but poor heat resistance.
[0392] (Comparative Example 3)
[0393] An amorphous sheet was obtained in the same manner as in Example 1 using polyester resin-E.
[0394] The sheet was stretched 3.0 times in the longitudinal direction at 70° C. Then, the film stretched in the longitudinal direction was introduced into a tenter, preheated at 65° C., and stretched 6.0 times in the width direction at 70° C. However, the film broke in the tenter, and no sample could be obtained.
[0395] (Comparative Example 4)
[0396] An amorphous sheet was obtained in the same manner as in Example 1 using the polyester resin-G.
[0397] The sheet was stretched to 3.0 times in the longitudinal direction at 100°C. Then, the film stretched in the longitudinal direction was introduced into a tenter, stretched to 3.1 times in the width direction at 110°C, and then heat-treated at 180°C and relaxed by 5% to obtain a biaxially stretched polyester film having a thickness of 20 μm. The obtained film had good stretchability, but poor heat resistance and impact strength.
[0398] (Comparative Example 5)
[0399] An amorphous sheet was obtained in the same manner as in Example 1 using the polyester resin-H.
[0400] The sheet was stretched to 3.0 times in the longitudinal direction at 105°C. The film stretched in the longitudinal direction was then heated at 100°C for 1 second, introduced into a tenter, stretched to 6.0 times in the width direction at 160°C, heat treated at 230°C, and relaxed by 7% to obtain a biaxially stretched polyester film having a thickness of 15 μm. The obtained film had good stretchability but poor impact strength.
[0401] (Comparative Example 6)
[0402] In Example 1, the same procedure as in Example 1 was performed except that the film was stretched in the width direction at 185° C. after preheating at 175° C. in the tentering step. However, the film broke in the tenter and no sample could be obtained.
[0403] Table 1 shows the film-forming conditions of the biaxially oriented polyester films of Examples 1 to 9 and Comparative Examples 1 to 6 and the evaluation results of the physical properties of the obtained films.
[0404] (Reference Example 1-1)
[0405] [1] Production of laminated biaxially oriented polyester film
[0406] The polyester resin-A was dried under reduced pressure (1 Torr) at 135° C. for 6 hours. Thereafter, the polyester resin-A was supplied to the extruder 1 , and 50 parts by weight of the polyester resin-A and 50 parts by weight of the polyester resin-K were dry-blended and supplied to the extruder 2 .
[0407] In the two extruders, the resin temperature was set to 280°C in the melting section, kneading section, piping, gear pump, and filter, and 275°C in the subsequent piping and T-die, and the melt was co-extruded from the T-die into a sheet, and cooled on a cooling roll at 40°C to obtain two kinds of two-layer amorphous sheets. The discharge amount and casting speed were adjusted to form sheets so that the resin thickness on the extruder 1 side and the resin thickness on the extruder 2 side were 200 μm and 100 μm, respectively.
[0408] The sheet was stretched to 3.5 times at 105°C in the longitudinal direction. Then, the film stretched in the longitudinal direction was introduced into a tenter, preheated at 140°C, stretched 6.0 times in the width direction at 150°C, heat treated at 215°C, and relaxed by 7% to obtain a biaxially stretched polyester film with an overall thickness of 15 μm. The resin layer on the extruder 2 side was used as a heat seal layer. The melting point difference between the extruder 1 side and the extruder 2 side was 50°C. The thickness of the seal layer was 5 μm.
[0409] The obtained film has good tensile properties, excellent heat resistance and impact strength. In addition, the obtained film is used as a cover material for a container to make a closed container as described below. There is no air leakage, etc., and a good closed container is obtained. For it, the recyclability is also good.
[0410] [2] Container manufacturing
[0411] First, a sheet with a thickness of 300 μm was obtained using the resin used in Example 1 on a pedestal machine. It should be noted that the diameter of the touch roll of the pedestal machine was 20 cm, the diameter of the cooling roll was 50 cm, and the total discharge amount of the resin to each layer was set to 50 kg / hour per 1 m of the table width. In addition, the roll speed was determined each time.
[0412] Next, the obtained 300 μm sheet was used in a vacuum pressure molding machine TVP-33 manufactured by Sanwa Kogyo Co., Ltd., using a mirror-finished mold to obtain a tray container filled with a capacity of 320 cc. It should be noted that the barrel temperature conditions during sheet molding were all set to 290° C., the sheet preheating conditions during container molding were all set to 90% heater power, the mold temperature conditions during container molding were all set to 180° C., and the heating time during container molding was all set to 10.5 seconds.
[0413] [3] Sealing of containers
[0414] The laminated axially oriented polyester film obtained in [1] was used as a lid material and sealed using Pack sealer SN1-N2 manufactured by Shinwa Machine to form a sealed container. The sealing process conditions by heat sealing are as follows.
[0415] Heat sealing temperature: 180℃
[0416] Heat sealing pressure: 0.5MPa
[0417] Heat sealing time: 1.0 seconds
[0418] [4] Sealing processability of containers and evaluation of the resulting sealed containers
[0419] The sealing processability of the container and the obtained sealed container were evaluated as follows. In any evaluation, 0 or △ was suitable for practical use.
[0420] (1) Sealing processability of the container
[0421] The cover material is attached, and the state of adhesion of the sealing portion of the sealed container is confirmed.
[0422] ○: Evenly attached
[0423] △: Some uneven areas such as wrinkles are visible
[0424] ×: The unpasted part is visible
[0425] (2) Confidentiality evaluation of sealed containers
[0426] Install the cover material, place the plate on the sealed container, and make the unit container bottom area 20g / cm 2 Place a weight on the test piece and check whether air is released after leaving it for 30 minutes.
[0427] ○: No change
[0428] △: Air separation is observed
[0429] ×: Cover peeled off
[0430] (3) Recyclability of sealed containers
[0431] The lid was installed, and 10 g of the sealed container was cut with scissors and placed in a test tube. The mixture was melted in a 300°C bath under a nitrogen atmosphere for 30 minutes while stirring. After that, the mixture was taken out of the test tube, opened to a thickness of about 100 μm, cooled to room temperature, and the transparency was evaluated.
[0432] ○: High transparency
[0433] △: Slightly turbid
[0434] ×: Low transparency
[0435] (Reference Example 1-2)
[0436] The polyester resin-A was dried under reduced pressure (1 Torr) at 135° C. for 6 hours. Thereafter, the polyester resin-A was supplied to the extruder 1 , and 55 parts by weight of the polyester resin-A and 45 parts by weight of the polyester resin-L were dry-blended and supplied to the extruder 2 .
[0437] In the two extruders, the resin temperature was set to 280°C in the melting section, kneading section, piping, gear pump, and filter, and 275°C in the subsequent piping and T-die. The resin on the extruder 1 side was melt-coextruded from the T-die to the cooling roll side, and cooled on a cooling roll at 40°C to obtain two kinds of two-layer amorphous sheets. The discharge amount and casting speed were adjusted to form sheets so that the resin thickness on the extruder 1 side and the resin thickness on the extruder 2 side were 240 μm and 60 μm, respectively.
[0438] The sheet was stretched to 3.5 times at 105°C in the longitudinal direction. Then, the film stretched in the longitudinal direction was introduced into a tenter, preheated at 140°C, stretched 6.0 times in the width direction at 150°C, heat treated at 215°C, and subjected to 7% relaxation treatment to obtain a biaxially stretched polyester film having an overall film thickness of 16 μm. The resin layer on the extruder 2 side was used as a sealing layer. The melting point difference between the extruder 1 side and the extruder 2 side was 45°C. The thickness of the sealing layer was 3 μm.
[0439] The obtained film has good tensile properties, and is also excellent in heat resistance and impact strength. In addition, the obtained film is used as a cover material for a container, and a closed container is made in the same manner as Reference Example 1-1. There is no air leakage, etc., and a good closed container is obtained. For it, recyclability is also good.
[0440] (Reference Example 1-3)
[0441] When producing polyester resin-A, plant-derived bio-ethylene glycol (made by Indiana glycol) was used instead of fossil-derived ethylene glycol to obtain the same polyester. This polyester resin was referred to as polyester resin-bio-A. Polyester resin-bio-A was dried under reduced pressure (1 Torr) at 135°C for 6 hours. Thereafter, polyester resin-bio-A was supplied to extruder 1, and 55 parts by weight of polyester resin-bio-A and 45 parts by weight of polyester resin-M were dry-blended and supplied to extruder 2.
[0442] In the two extruders, the resin temperature was set to 280°C in the melting section, kneading section, piping, gear pump, and filter, and 275°C in the subsequent piping and T-die. The resin on the extruder 1 side was melt-coextruded from the T-die to the cooling roll side, and cooled on a cooling roll at 40°C to obtain two kinds of two-layer amorphous sheets. The discharge amount and casting speed were adjusted to form sheets so that the resin thickness on the extruder 1 side and the resin thickness on the extruder 2 side were 240 μm and 60 μm, respectively.
[0443] The sheet was stretched to 3.5 times at 105°C in the longitudinal direction. Then, the film stretched in the longitudinal direction was introduced into a tenter, preheated at 140°C, stretched 6.0 times in the width direction at 150°C, heat treated at 215°C, and subjected to 7% relaxation treatment to obtain a biaxially stretched polyester film with an overall thickness of 18 μm. The resin layer on the extruder 2 side was used as a sealing layer. The melting point difference between the extruder 1 side and the extruder 2 side was 40°C. The thickness of the sealing layer was 3 μm.
[0444] The obtained film has good tensile properties, and is also excellent in heat resistance and impact strength. In addition, the obtained film is used as a cover material for a container, and a closed container is made in the same manner as Reference Example 1-1. There is no air leakage, etc., and a good closed container is obtained. For it, recyclability is also good.
[0445] (Reference Example 1-4)
[0446] The polyester resin-A was dried under reduced pressure (1 Torr) at 135° C. for 6 hours. Thereafter, the polyester resin-A was supplied to the extruder 1 , and 55 parts by weight of the polyester resin-A and 45 parts by weight of the polyester resin-M were dry-blended and supplied to the extruder 2 .
[0447] In the two extruders, the resin temperature was set to 280°C in the melting section, kneading section, piping, gear pump, and filter, and 275°C in the subsequent piping and T-die. The resin on the extruder 1 side was melt-coextruded from the T-die to the cooling roll side, and cooled on a cooling roll at 40°C to obtain two kinds of two-layer amorphous sheets. The discharge amount and casting speed were adjusted to form sheets so that the resin thickness on the extruder 1 side and the resin thickness on the extruder 2 side were 240 μm and 3 μm, respectively.
[0448] The sheet was stretched to 3.5 times at 105°C in the longitudinal direction. Then, the film stretched in the longitudinal direction was introduced into a tenter, preheated at 140°C, stretched 6.0 times in the width direction at 150°C, heat treated at 215°C, and subjected to 7% relaxation treatment to obtain a biaxially stretched polyester film with an overall thickness of 12 μm. The resin layer on the extruder 2 side was used as a sealing layer. The melting point difference between the extruder 1 side and the extruder 2 side was 40°C. The thickness of the sealing layer was 0.1 μm.
[0449] The obtained film has good stretchability, excellent heat resistance and impact strength. In addition, the obtained film was used as a cover material for a container to make a sealed container in the same manner as Reference Example 1-1, but air leakage occurred due to the load. The recyclability was good.
[0450] (Reference Example 1-5)
[0451] Polyester resin-A was dried under reduced pressure (1 Torr) at 135° C. for 6 hours. Then, polyester resin-bio-A was supplied to extruder 1 , and 55 parts by weight of polyester resin-A and 45 parts by weight of polyester resin-M were dry-blended and supplied to extruder 2 .
[0452] In the two extruders, the resin temperature in the melting section, kneading section, piping, gear pump, and filter was set to 280°C, and in the subsequent piping and T-die to 275°C. The resin on the extruder 1 side was melt-coextruded from the T-die to the cooling roll side, and cooled on a cooling roll at 40°C to obtain two kinds of two-layer amorphous sheets. The discharge amount and casting speed were adjusted to form sheets so that the resin thickness on the extruder 1 side and the resin thickness on the extruder 2 side were 150 μm and 150 μm, respectively.
[0453] The sheet was stretched to 3.5 times at 105°C in the longitudinal direction. Then, the film stretched in the longitudinal direction was introduced into a tenter, preheated at 140°C, stretched 6.0 times in the width direction at 150°C, heat treated at 215°C, and subjected to 7% relaxation treatment to obtain a biaxially stretched polyester film with an overall thickness of 30 μm. The resin layer on the extruder 2 side was used as a sealing layer. The melting point difference between the extruder 1 side and the extruder 2 side was 40°C. The thickness of the sealing layer was 15 μm.
[0454] The obtained film had good tensile properties, excellent heat resistance and impact strength. In addition, the obtained film was used as a cover material for a container, and a sealed container was prepared in the same manner as Reference Example 1-1. There was no air leakage, etc., and a good sealed container was obtained, but for it, white turbidity was observed during recycling, and the recycling property was poor.
[0455] Tables 2 and 3 show the film-forming conditions of the laminated biaxially oriented polyester films of Reference Examples 1-1 to 1-5 and the evaluation results of the physical properties of the obtained films.
[0456] [Table 1]
[0457]
[0458] [Table 2]
[0459]
[0460] ※1: Thermal shrinkage after heat treatment at 120°C for 30 minutes
[0461] ※2: Evaluation at heat sealing temperature of 125℃
[0462] ※3: Describes the relationship between the composition, physical properties, and conditions of the substrate side
[0463] ※4: Melt flow index (210℃, 2.16kg) is used as a substitute for viscosity.
[0464] ※5: Viscosity on the film substrate side
[0465] [Table 3]
[0466]
Claims
1. A method for producing a biaxially stretched polyester film, comprising the following steps A to D, Tc represents the crystallization temperature, Tg represents the glass transition temperature, and Tm represents the melting point. The unit of the temperature is °C. Step A: a step of melt-extruding a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C or higher and 35°C or lower to obtain an unstretched polyester resin composition sheet, Step B: heating the unstretched polyester resin composition sheet obtained in step A within a range of Tg of the polyester resin + 5°C or higher and Tg of the polyester resin + 40°C or lower, and stretching the sheet in the longitudinal direction within a range of a stretching ratio of 2 to 6 times to obtain a uniaxially oriented polyester resin composition film. Step C: heating the uniaxially oriented polyester resin composition film obtained in step B within a range of Tc-46°C or higher and Tc+25°C or lower of the polyester resin, and stretching the film in the width direction within a range of a stretching ratio of 4 to 8 times to obtain a biaxially oriented polyester resin composition film, Step D: A step of relaxing the biaxially oriented polyester resin composition film obtained in step C within a range of 3% to 20% in the width direction of the film while heating the film within a range of Tm-40°C to Tm-5°C of the polyester resin.
2. A method for producing a biaxially stretched polyester film, comprising the following steps A to D, Tc represents the crystallization temperature, Tg represents the glass transition temperature, and Tm represents the melting point. The unit of the temperature is °C. Step A: a step of melt-coextruding a layer formed of a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C or higher and 35°C or lower and a layer formed of a polyester resin composition to obtain an unstretched polyester resin composition sheet, Step B: heating the unstretched polyester resin composition sheet obtained in step A within a range of Tg of the polyester resin + 5°C or higher and Tg of the polyester resin + 40°C or lower, and stretching the sheet in the longitudinal direction within a range of a stretching ratio of 2 to 6 times to obtain a uniaxially oriented polyester resin composition film. Step C: heating the uniaxially oriented polyester resin composition film obtained in step B within a range of Tc-46°C or higher and Tc+25°C or lower of the polyester resin, and stretching the film in the width direction within a range of a stretching ratio of 4 to 8 times to obtain a biaxially oriented polyester resin composition film, Step D: A step of relaxing the biaxially oriented polyester resin composition film obtained in step C within a range of 3% to 20% in the width direction of the film while heating the film within a range of Tm-40°C to Tm-5°C of the polyester resin.
3. A biaxially oriented polyester film, which is formed from a composition comprising a polyester resin having a Tc-(Tg+Tm) / 2 of not less than -25°C and not more than 35°C, and satisfies the following (1) to (3), Tc represents the crystallization temperature, Tg represents the glass transition temperature, and Tm represents the melting point. The unit of the temperature is °C. (1) The maximum value of the heat shrinkage stress in the longitudinal direction above Tg°C of the polyester resin is 0.1 MPa to 4.0 MPa, (2) when treated at 150°C for 30 minutes, the heat shrinkage in the longitudinal direction is 0.1% or more and 3.0% or less, (3) Impact strength is 0.5 J / 12 μm or more and 1.0 J / 12 μm or less.
4. A biaxially oriented polyester film comprising: a layer formed from a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of not less than -25°C and not more than 35°C, and a layer formed from a polyester resin composition, and satisfying the following (1) to (3), Tc represents the crystallization temperature, Tg represents the glass transition temperature, and Tm represents the melting point. The unit of the temperature is °C. (1) The maximum value of the heat shrinkage stress in the longitudinal direction above Tg°C of the polyester resin is 0.1 MPa to 4.0 MPa, (2) when treated at 150°C for 30 minutes, the heat shrinkage in the longitudinal direction is 0.1% or more and 3.0% or less, (3) Impact strength is 0.5 J / 12 μm or more and 1.0 J / 12 μm or less.
5. A method for producing a biaxially oriented polyester film satisfying the following (1) to (3), comprising the following steps A to D, Tc represents the crystallization temperature, Tg represents the glass transition temperature, and Tm represents the melting point. The unit of the temperature is °C. (1) The maximum value of the heat shrinkage stress in the longitudinal direction above Tg°C of the polyester resin is 0.1 MPa to 4.0 MPa, (2) when treated at 150°C for 30 minutes, the heat shrinkage in the longitudinal direction is 0.1% or more and 3.0% or less, (3) Impact strength is 0.5 J / 12 μm or more and 1.0 J / 12 μm or less, Step A: a step of melt-extruding a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C or higher and 35°C or lower to obtain an unstretched polyester resin composition sheet, Step B: heating the unstretched polyester resin composition sheet obtained in step A within a range of Tg of the polyester resin + 5°C or higher and Tg of the polyester resin + 40°C or lower, and stretching the sheet in the longitudinal direction within a range of a stretching ratio of 2 to 6 times to obtain a uniaxially oriented polyester resin composition film. Step C: heating the uniaxially oriented polyester resin composition film obtained in step B within a range of Tc-46°C or higher and Tc+25°C or lower of the polyester resin, and stretching the film in the width direction within a range of a stretching ratio of 4 to 8 times to obtain a biaxially oriented polyester resin composition film, Step D: A step of relaxing the biaxially oriented polyester resin composition film obtained in step C within a range of 3% to 20% in the width direction of the film while heating the film within a range of Tm-40°C to Tm-5°C of the polyester resin.
6. A method for producing a biaxially oriented polyester film satisfying the following (1) to (3), comprising the following steps A to D, Tc represents the crystallization temperature, Tg represents the glass transition temperature, and Tm represents the melting point. The unit of the temperature is °C. (1) The maximum value of the heat shrinkage stress in the longitudinal direction above Tg°C of the polyester resin is 0.1 MPa to 4.0 MPa, (2) when treated at 150°C for 30 minutes, the heat shrinkage in the longitudinal direction is 0.1% or more and 3.0% or less, (3) Impact strength is 0.5 J / 12 μm or more and 1.0 J / 12 μm or less, Step A: a step of melt-coextruding a layer formed of a composition containing a polyester resin having a Tc-(Tg+Tm) / 2 of -25°C or higher and 35°C or lower and a layer formed of a polyester resin composition to obtain an unstretched polyester resin composition sheet, Step B: heating the unstretched polyester resin composition sheet obtained in step A within a range of Tg of the polyester resin + 5°C or higher and Tg of the polyester resin + 40°C or lower, and stretching the sheet in the longitudinal direction within a range of a stretching ratio of 2 to 6 times to obtain a uniaxially oriented polyester resin composition film. Step C: heating the uniaxially oriented polyester resin composition film obtained in step B within a range of Tc-46°C or higher and Tc+25°C or lower of the polyester resin, and stretching the film in the width direction within a range of a stretching ratio of 4 to 8 times to obtain a biaxially oriented polyester resin composition film, Step D: A step of relaxing the biaxially oriented polyester resin composition film obtained in step C within a range of 3% to 20% in the width direction of the film while heating the film within a range of Tm-40°C to Tm°C of the polyester resin.
Citation Information
Patent Citations
Biaxially stretched polyethylene terephthalate-based film and method for producing the same
JP2017074750A
Biaxially stretched polyester film, and production method therefor
CN107530952A
Liquid transportation system for microfluidic device
US6368562B1